Laminated polyester film
By forming a resin layer composed of low-polar compounds, binder resins and crosslinking agents on the polyester film, the problem of poor wrinkles and slippage of the polyester film when curled is solved, and the formation and treatmentability of the subtle uneven structure are improved, supporting the increase in the thickness and production efficiency of the polyester film.
Patent Information
- Application Number
- JP2023120138
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
AI Technical Summary
The existing polyester films are prone to wrinkles and poor sliding properties when curled, resulting in poor handling and difficult to form subtle uneven structures in the film, affecting the stability of the manufacturing process and product quality.
A resin layer consisting of a low polarity compound, a binder resin and a crosslinker is formed on one or both sides of the polyester film. A fine uneven structure is formed by phase separation to ensure that the surface roughness and air leakage index of the resin layer are within an acceptable range.
The coating adhesion and handling properties of the polyester film are improved, wrinkles and slippage problems during curling are reduced, and the thickness of the polyester film is increased and production efficiency is improved.
Smart Images

Figure 2025017183000001 
Figure 2025017183000002 
Figure 2025017183000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated polyester film. [Background technology]
[0002] Polyester films, typified by polyethylene terephthalate films and polyethylene naphthalate films, have excellent properties such as mechanical properties, dimensional stability, flatness, heat resistance, chemical resistance, optical properties, etc., and also have excellent cost performance, so they are used for various purposes.
[0003] In addition, polyester films are favorably used for various applications, such as release films for molding green sheets for multilayer ceramic capacitors, substrates for releasing interlayer insulating resins, and substrates for dry film resists, taking advantage of the smoothness of the film surface.
[0004] Polyester films for sheet molding having excellent surface smoothness for the above-mentioned applications and other uses are required to be wrinkle-free and have a good roll appearance when wound into a roll. However, increasing the surface smoothness reduces the slipperiness and reduces the ability of the film to escape air when wound into a roll or when unwound from the roll, resulting in slippage and blocking, which reduces the handling properties. In particular, in recent years, with the improvement in productivity, there has been a trend toward thinner and longer polyester films, which requires a higher level of roll appearance quality.
[0005] Therefore, in order to ensure ease of handling, the non-smooth side (back side) is sometimes designed to be rougher than the smooth side by kneading particles into it (for example, Patent Document 1). Patent Document 2 discloses a back resin layer having a surface on the back side thereof in which recesses are formed by a sea-island structure and in which the arithmetic mean roughness (Ra) is 10 to 80 nm. Furthermore, Patent Documents 3 and 4 disclose laminated films having a concave-convex layer formed by phase separation.
[0006] However, in the conventional particle-incorporated film manufacturing method as disclosed in Patent Document 1, it is difficult to control the formation of unevenness, and it is difficult to form a fine uneven structure. Furthermore, the films disclosed in Patent Documents 2 to 4 have problems in that they are hardly capable of being said to have a fine uneven structure, and the layer having the unevenness is thick.
[0007] More specifically, if the film does not have a fine uneven structure, wrinkles are likely to occur when the film is wound into a roll, which may impair the appearance of the roll. Furthermore, if the layer having projections and recesses is thick, the flatness may be impaired due to curling caused by cure shrinkage, and such a method may not be suitable for making a thin, long polyester film.
[0008] Furthermore, for example, in the manufacturing process of green sheets for multilayer ceramic capacitors, there are problems such as the inherent performance of the laminated polyester film being impaired due to peeling or falling off of the coating film, and the manufacturing process being contaminated by the fallen coating film. Therefore, in laminated polyester films, the adhesion and adhesion between the base film and the coating film formed thereon are important, and it is required that the coating film does not easily fall off, i.e., that the retention rate of the coating film is high. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2015-33811 A [Patent Document 2] JP 2013-60555 A [Patent Document 3] JP 2013-10323 A [Patent Document 4] Patent Publication No. 2021-24177 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made in consideration of the above-mentioned circumstances, and an object of the present invention is to provide a laminated film which has a high coating film retention rate and is resistant to peeling. Further, the present invention aims to provide a laminated polyester film which has a high coating retention rate, is capable of forming a fine uneven structure even when it is a thin film, and has excellent handling properties when the film is wound into a roll. [Means for solving the problem]
[0011] As a result of intensive research, the present inventors have found that the above problems can be solved by the following configuration. The present invention has the following aspects.
[0012] [1] A laminated polyester film having a resin layer formed from a resin composition on at least one side of a polyester film, wherein the polar component term in the surface free energy of the resin layer is 5 mN / m or less. [2] The laminated polyester film according to the above [1], wherein the resin composition further contains (A) a low-polarity compound. [3] The laminated polyester film according to the above [1] or [2], wherein the resin composition further contains a binder resin (B). [4] The laminated polyester film according to any one of the above [1] to [3], wherein the resin composition further contains a crosslinking agent (C). [5] The laminated polyester film according to any one of the above [1] to [4], wherein the load length ratio (Rmr(90)) of the roughness curve at a cutting level of 90% of the surface of the resin layer is 95% or less when measured with a scanning probe microscope. [6] The laminated polyester film according to any one of the above [1] to [5], wherein the arithmetic average roughness (Ra) of the surface of the resin layer is 15 nm or more when measured with a scanning probe microscope. [7] The laminated polyester film according to any one of the above [1] to [6], wherein the ten-point average roughness (Rzjis) of the surface of the resin layer as measured by a scanning probe microscope is 70 nm or more. [8] The laminated polyester film according to any one of the above [1] to [7], wherein the resin layer has an uneven structure. [9] The laminated polyester film according to any one of the above [1] to [8], which has an air leakage index of 190,000 seconds or less.
[10] The laminated polyester film according to any one of the above [2] to [9], wherein the (A) low-polarity compound includes at least one member selected from the group consisting of wax and a compound containing a long-chain alkyl group.
[11] The laminated polyester film according to any one of the above [3] to
[10] , wherein the (B) binder resin comprises at least one resin selected from the group consisting of polyester resins, (meth)acrylic resins, and polyurethane resins.
[12] The laminated polyester film according to any one of the above [4] to
[11] , wherein the (C) crosslinking agent is a melamine compound.
[13] The laminated polyester film according to any one of the above [1] to
[12] , wherein the resin composition contains (D) a crosslinking catalyst.
[14] The laminated polyester film according to any one of the above [1] to
[13] , wherein the resin composition contains (E) particles.
[15] The laminated polyester film according to any one of the above [1] to
[14] , which is used as a support for a ceramic green sheet in a production process of a laminated ceramic capacitor.
[16] Use of the laminated polyester film according to any one of the above [1] to
[15] as a support for a ceramic green sheet in a process for producing a laminated ceramic capacitor.
[17] A method for producing a ceramic green sheet, comprising coating a slurry containing a ceramic component on a surface of the laminated polyester film according to any one of the above [1] to
[15] opposite to the resin layer. Effect of the Invention
[0013] According to the present invention, it is possible to provide a laminated film which has a high coating film retention rate and is resistant to peeling. Furthermore, it is possible to provide a laminated polyester film which has a high coating film retention rate, can form a fine uneven structure even when the film is thin, and has excellent handleability when the film is wound into a roll.
[0014] In addition, since the resin layer surface of the laminated polyester film of the present invention has a fine uneven structure and has excellent coating strength, when used for sheet molding, for example, the extremely smooth film has the advantage of exhibiting good winding properties and being less likely to cause wrinkles even when wound into a roll. Furthermore, since the resin layer of the laminated polyester film of the present invention can be made thin, it can also accommodate thin and long polyester films, which can contribute to improving productivity by reducing the frequency of changing product rolls during processing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Next, an example of an embodiment of the present invention will be described, however, the present invention is not limited to the embodiment described below.
[0016] In this specification, when the expression "(meth)acrylic" is used, "(meth)acrylic" means one or both of "acrylic" and "methacrylic". Similarly, "(meth)acrylic acid" means one or both of "acrylic acid" and "methacrylic acid", "(meth)acrylate" means one or both of "acrylate" and "methacrylate", and "(meth)acryloyl" means one or both of "acryloyl" and "methacryloyl". The same applies to the other terms.
[0017] <<<Laminated polyester film>>> The laminated polyester film of the present invention (hereinafter also referred to as "the present laminated polyester film") comprises a polyester film (hereinafter also referred to as "the present polyester film") and a resin layer (hereinafter also referred to as "the present resin layer") formed from a resin composition on at least one side of the polyester film.
[0018] The laminated structure of the present laminated polyester film may be a structure in which a resin layer is formed on one side of a polyester film and the surface of the polyester film is left as is on the other side, or a structure in which another layer is formed on the other side. Alternatively, a resin layer may be formed on both sides of a polyester film. Furthermore, the resin layer may be formed directly on the polyester film, or another layer may be provided between the polyester film and the resin layer.
[0019] <<Polyester film>> The polyester film serves as a substrate for the laminated polyester film. The polyester film may be a single layer or a multilayer. When the polyester film has a multilayer structure, the polyester film may have a two-layer structure, a three-layer structure, or a four-layer structure or more without departing from the gist of the present invention. The number of layers is not particularly limited. When the polyester film has a multi-layer structure of two or more layers, a two-kind three-layer structure or a three-kind three-layer structure is particularly preferable. When the polyester film has a multi-layer structure, it is also preferable that the polyester film has a structure in which surface layers are provided on both sides of an intermediate layer.
[0020] In particular, when utilizing the smoothness of the laminated polyester film, it is preferable that at least one side of the polyester film has excellent smoothness. Examples of such design methods include a method of designing the polyester film to have a single layer, two-kind three-layer, or three-kind three-layer structure so that both sides of the polyester film have excellent smoothness, and a method of designing the polyester film to have a three-kind three-layer structure so that one side of the polyester film has excellent smoothness and the other side has a different roughness.
[0021] The polyester film may be a non-stretched film (sheet) or a stretched film. Of these, a uniaxially or biaxially stretched film is preferred. Of these, a biaxially stretched film is more preferred in terms of excellent balance of mechanical properties and flatness.
[0022] <Polyester> The polyester, which is the raw material of the polyester film, refers to a polymeric compound having continuous ester bonds in the main chain, and may be a homopolyester or a copolymer polyester. Specifically, a polyester obtained by polycondensation reaction of a dicarboxylic acid component and a diol component can be mentioned. In addition, it is preferable to use a polyester containing more than 50 mol% of an aromatic dicarboxylic acid or an aliphatic dicarboxylic acid when the dicarboxylic acid component is taken as 100 mol%.
[0023] Examples of the dicarboxylic acid component include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and 4,4'-diphenylsulfonedicarboxylic acid, and aliphatic dicarboxylic acids such as adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, cyclohexanedicarboxylic acid, and ester derivatives thereof.
[0024] Examples of the diol component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-hexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2-bis(4-hydroxyethoxyphenyl)propane, isosorbate, and spiroglycol.
[0025] When the polyester is a homopolyester, it is preferably one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic diol. As the aromatic dicarboxylic acid, preferably, terephthalic acid, 2,6-naphthalenedicarboxylic acid, etc. are mentioned, and as the aliphatic diol, preferably, ethylene glycol, diethylene glycol, 1,4-cyclohexanedimethanol, etc. are mentioned. As a representative homopolyester, polyethylene terephthalate (PET), polyethylene-2,6-naphthalenedicarboxylate (PEN), etc. can be mentioned, and polyethylene terephthalate is preferable.
[0026] On the other hand, the copolymer polyester is preferably a polycondensation polymer of a dicarboxylic acid component and an aliphatic diol. The dicarboxylic acid component is preferably one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, and oxycarboxylic acid (e.g., p-oxybenzoic acid, etc.). The aliphatic diol is preferably one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, and neopentyl glycol. The copolymer polyester more preferably contains terephthalic acid as the dicarboxylic acid component and ethylene glycol as the aliphatic diol. When the polyester is a copolymer polyester, it is preferable that the polyester is a copolymer containing 30 mol % or less of a third component. The third component is a component other than the compound that is the main component (i.e., the component with the largest content) of the dicarboxylic acid component constituting the polyester and the compound that is the main component of the diol component, and for example, in the case of copolymerized polyethylene terephthalate, it is a component other than terephthalic acid and ethylene glycol. The copolymer polyester may also contain a structural unit derived from a difunctional compound other than a dicarboxylic acid component and an aliphatic diol. The structural unit derived from a difunctional compound other than a dicarboxylic acid component and an aliphatic diol is preferably 20 mol% or less, more preferably 10 mol% or less, based on the total moles of all structural units constituting the polyester. Examples of the bifunctional compound include various hydroxycarboxylic acids and aromatic diols.
[0027] The content of terephthalic acid in all dicarboxylic acid components constituting the present polyester film is preferably 50 mol % or more, more preferably 70 mol % or more, and further preferably 90 mol % or more. The content of ethylene glycol in all diol components constituting the present polyester film is preferably 50 mol % or more, more preferably 70 mol % or more, and further preferably 90 mol % or more. The upper limit of the content of terephthalic acid and ethylene glycol is 100 mol %.
[0028] The polyester may be a recycled polyester or a biomass-derived polyester.
[0029] <Polycondensation catalyst> The polycondensation catalyst used in polycondensing the polyester is not particularly limited, and any conventionally known compound can be used. Examples of the polycondensation catalyst include titanium compounds, germanium compounds, antimony compounds, manganese compounds, aluminum compounds, magnesium compounds, and calcium compounds. Among these, at least one of titanium compounds and antimony compounds is preferred, and it is particularly preferred to use a polyester obtained by using a titanium compound. Therefore, the present polyester film preferably contains at least one of a titanium compound and an antimony compound, and more preferably contains a titanium compound.
[0030] By using the titanium compound, the amount of antimony compound used can be reduced, which reduces the risk of new protrusions being formed due to the antimony compound precipitating on the film surface, and allows a high level of surface smoothness to be maintained. Therefore, in a particularly preferred embodiment, when the present polyester film has a multi-layer structure, the titanium compound is used for the polyester constituting at least one of the surface layers.
[0031] The titanium element content derived from the titanium compound in the surface layer is preferably 3 ppm to 40 ppm, more preferably 4 ppm to 35 ppm, based on mass. When the surface layer contains at least one of an antimony compound and a titanium compound, the antimony element content in the surface layer is preferably 0 ppm to 100 ppm. Within this range, it is possible to reduce the amount of foreign matter caused by the catalyst without reducing the production efficiency. From the viewpoint of productivity and cost, it is also preferable that the polyester constituting the layers other than the surface layer does not contain a titanium compound. As described above, by including a titanium compound in the polyester film, it is possible to obtain a polyester film having excellent smoothness. In addition, when the polyester film is made into a laminated polyester film having the resin layer, the laminated polyester film can be suitably used for forming a sheet or the like.
[0032] <Intrinsic viscosity> The intrinsic viscosity (IV) of the polyester constituting the present polyester film is preferably 0.5 dL / g or more, more preferably 0.55 dL / g or more, and even more preferably 0.6 dL / g or more. If it is within such a range, there is an advantage that the particles are highly dispersed by increasing the shear stress during kneading. In addition, the intrinsic viscosity (IV) of the polyester is, for example, 1 dL / g or less, preferably 0.8 dL / g or less, and more preferably 0.7 dL / g or less. In addition, when two or more polyesters with different intrinsic viscosities (IV) are used, the "intrinsic viscosity (IV) of the polyester constituting the present polyester film" means the intrinsic viscosity (IV) of the mixed polyesters.
[0033] When the present polyester film has a multi-layer structure, it is preferable that the intrinsic viscosity (IV) of the polyester constituting the surface layer is within the above range.
[0034] <particle> The polyester film may contain particles, which imparts slipperiness to the polyester film and prevents scratches during each process, improving the handling properties. The type of particles contained in the polyester film is not particularly limited as long as it is a particle capable of imparting slipperiness, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, as well as crosslinked polymers such as crosslinked silicone resin particles, crosslinked acrylic resin particles, crosslinked styrene-acrylic resin particles, and crosslinked polyester particles, and organic particles such as calcium oxalate and ion exchange resin. Among these, organic particles, silica, aluminum oxide, and the like are preferred. Among these, it is preferred to include aluminum oxide from the viewpoint of hardening the layer to prevent the film surface from being scratched and maintaining smoothness. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process can also be used.
[0035] The shape of the particles to be used is not particularly limited, and any of spherical, block, rod-like, flat, etc. may be used. There is also no particular limitation on the hardness, specific gravity, color, etc. Two or more kinds of these particles may be used in combination as necessary.
[0036] The average particle size of the particles used is usually 5 μm or less, preferably 0.01 to 3 μm, more preferably 0.02 to 1 μm, and even more preferably 0.03 to 0.5 μm. If the average particle size is 5 μm or less, the surface roughness of the film does not become too rough, and problems are less likely to occur when forming a resin layer and various surface functional layers other than the resin layer in a later process, and this is preferable. If the average particle size is within this range, the haze is kept low, and the transparency of the entire laminated polyester film is easily ensured. The average particle size of particles can be determined by measuring the diameters of 10 or more particles using a scanning electron microscope (SEM) and averaging the diameters. In the case of non-spherical particles, the average of the longest and shortest diameters can be measured as the diameter of each particle.
[0037] When particles are incorporated into the polyester film, it is preferable to incorporate particles into the surface layer, for example, by providing a surface layer and an intermediate layer. In addition, when the front and back layers are differently designed, such as a three-type three-layer structure, it is also possible to incorporate particles into at least one of the surface layers. The content of the particles depends on the average particle size, but is usually 5000 ppm or less, preferably 3000 ppm or less, more preferably 1000 ppm or less, based on mass in the layer containing the particles. When the particles are not contained or the content of the particles is small, the slipperiness cannot be sufficiently imparted, and the transparency of the polyester film is high, but the slipperiness may be insufficient. Therefore, it is necessary to improve the slipperiness by laminating the present resin layer described later. In addition, if it is 5000 ppm or less, the transparency of the polyester film can be sufficiently guaranteed. In addition, in the layer containing the resin, the content of the particles is not particularly limited, and is, for example, 50 ppm or more, preferably 100 ppm or more.
[0038] The resin layer described later may be provided on a layer of the polyester film containing particles, or may be provided on a layer that does not substantially contain particles. In addition, the surface (opposite surface) of the polyester film opposite to the surface on which the resin layer is provided may be a layer that does not substantially contain particles, or may be a layer that contains particles. In the present invention, even if both the surface on which the resin layer is provided and the opposite surface are layers that do not substantially contain particles, the winding properties can be improved by the resin layer having the uneven structure described later. In addition, by making one or both of the surface on which the resin layer is provided and the opposite surface into layers that contain particles, the winding properties can be further improved. In order to impart excellent smoothness to at least one surface of the present polyester film, the surface layer on the smooth side may contain particles or may be substantially free of particles, but in order to obtain a film with extremely high smoothness, it is preferable that the surface layer be substantially free of particles. Incidentally, "substantially not contained" means not intentionally contained, and specifically refers to the particle content (particle concentration) being less than 50 ppm by mass, more preferably 40 ppm or less, and even more preferably 30 ppm or less. In this case, by laminating the present resin layer on the surface layer on the smooth surface side and / or on the surface layer on the opposite side to the smooth surface, the handling properties when the film is wound into a roll can be improved. From the viewpoint of improving the handling properties while maintaining the smoothness of the film, it is preferable to make at least one side smooth and laminate the present resin layer on the opposite side.
[0039] The method of adding particles to the polyester film is not particularly limited, and any conventionally known method can be adopted. For example, in the case of a multi-layer polyester film, the particles can be added at any stage of the production of the polyester constituting each layer, but it is preferable to add the particles after the completion of the esterification or transesterification reaction.
[0040] <Other> In order to suppress the amount of precipitation of oligomer components, the film may be produced using a polyester having a low content of oligomer components as the raw material. As a method for producing a polyester having a low content of oligomer components, various known methods can be used, such as a method of performing solid phase polymerization after the production of a polyester. The amount of precipitation of oligomer components may be suppressed by forming the present polyester film into a three or more layer structure and forming a surface layer of the present polyester film using a polyester raw material having a low content of oligomer components. The polyester may also be obtained by carrying out the esterification or transesterification reaction, followed by melt polycondensation at a higher reaction temperature under reduced pressure.
[0041] In addition to the above-mentioned particles, conventionally known ultraviolet absorbents, antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, etc. may be added to the polyester film, if necessary.
[0042] The thickness of the polyester film is not particularly limited as long as it is within a range that allows the film to be formed, but from the viewpoints of mechanical strength, handleability, productivity, etc., the thickness is preferably 1 μm or more, more preferably 10 μm or more, even more preferably 19 μm or more, particularly preferably 25 μm or more, and is preferably 200 μm or less, more preferably 125 μm or less, even more preferably 80 μm or less, particularly preferably 50 μm or less.
[0043] <Production method of polyester film> Next, a production example of the present polyester film will be specifically described, but the production example is not limited to the following production example. For example, when producing a biaxially stretched film, a method is preferred in which the dried pellets of the above-mentioned polyester raw material are extruded as a molten sheet from a die using a melt extrusion device such as an extruder, and cooled and solidified by a cooling roll such as a rotating cooling drum to obtain an unstretched sheet. In this case, it is preferable to increase the adhesion between the sheet and the cooling roll in order to improve the flatness of the sheet, and an electrostatic application adhesion method and / or a liquid application adhesion method are preferably used.
[0044] Next, the obtained unstretched sheet is stretched in biaxial directions. In this case, the unstretched sheet is first stretched in one direction by a roll or tenter type stretching machine. The stretching temperature is usually 70 to 120°C, preferably 80 to 110°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3 to 6 times. Then, the film is stretched in a direction perpendicular to the first-stage stretching direction. In this case, the stretching temperature is usually 70 to 170° C., and the stretch ratio is usually 3 to 7 times, preferably 3.5 to 6 times. Then, the film is heat-treated under tension or relaxation of 30% or less at a temperature of 180 to 270° C. to obtain a biaxially stretched film. This heat treatment is also called a heat setting step. The heat treatment may be performed in two or more steps with different temperatures. After the heat treatment, the film may be cooled in a cooling zone. The cooling temperature is preferably higher than the glass transition temperature (Tg) of the polyester constituting the film, and more specifically, is preferably in the range of 100 to 160° C. This cooling may be performed in two or more steps at different temperatures. In the above stretching, a method of stretching in one direction in two or more stages can be adopted. In that case, it is preferable to perform the stretching so that the final stretch ratios in both directions are each within the above range.
[0045] The polyester film may also be produced by a simultaneous biaxial stretching method, which involves simultaneously stretching and orienting the unstretched sheet in the machine direction (longitudinal direction) and width direction (transverse direction) under temperature control usually at 70 to 120° C., preferably 80 to 110° C., and the stretching ratio is preferably 4 to 50 times, more preferably 7 to 35 times, and even more preferably 10 to 25 times in terms of area ratio. Then, the film is subsequently heat-treated under tension or under relaxation of 30% or less at a temperature of 170 to 250° C. to obtain a stretched and oriented film. Regarding the simultaneous biaxial stretching device employing the above-mentioned stretching method, a conventionally known stretching method such as a screw method, a pantograph method, or a linear drive method can be employed.
[0046] <<Resin layer>> The laminated polyester film of the present invention comprises a resin layer formed from a resin composition on at least one side of a polyester film. The resin layer may be a cured resin layer. As described above, the present resin layer is formed from a resin composition (hereinafter also referred to as "the present composition"), and preferably has an uneven structure.
[0047] <Uneven structure> The uneven structure of the resin layer is preferably a fine shape formed by phase separation. The unevenness caused by phase separation occurs when a composition made of resins with different compatibility undergoes phase separation of the resin components themselves in the resin composition and / or during the process of coating, stretching, drying, curing, heat treatment, etc., thereby forming an uneven structure on the surface. More specifically, the uneven structure is formed by the formation of recesses or protrusions by phase separation on the surface. The structure can be confirmed by various surface analysis techniques, such as an atomic force microscope (scanning probe microscope).
[0048] In the present invention, the term "resin" refers to a main component involved in film formation. More specifically, the "resin" includes the components (A) and (B) described below.
[0049] <Resin composition> The present composition preferably contains the following component (A), and preferably contains, in addition to the following component (A), the following component (B) and / or the following component (C), and more preferably contains the following components (A), (B) and (C). (A) Low polarity compound (B) Binder resin (C) Crosslinking agent
[0050] The total content of components (A), (B) and (C) contained in the composition is preferably 50% by mass or more as non-volatile components. More preferably, it is 55% by mass or more, even more preferably 60% by mass or more, and even more preferably 65% by mass or more. If the total content is within this range, the effect of phase separation is fully exerted, and the desired fine uneven structure is easily obtained. The total content of components (A), (B) and (C) is not particularly limited in terms of the upper limit, and may be 100% by mass or less, but is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less, and even more preferably 80% by mass or less.
[0051] (((Component (A)))) This composition contains (A) a low polarity compound (component (A)). The compatibility of the (A) low polarity compound with the (B) binder resin and / or (C) crosslinking agent (hereinafter sometimes referred to as "component (B) etc.") described later is also taken into consideration. If the compatibility is good, the component (A) is likely to be relatively dispersed and present in the component (B) etc. On the other hand, if the compatibility between the (A) low polarity compound and the component (B) etc. is poor, the (A) low polarity compound is likely to be unevenly distributed on the surface of the resin layer. In other words, the uneven distribution of the low polarity component on the surface reduces the polarity component term in the surface free energy of the resin layer, making it easier to achieve the effects of the present invention. Therefore, there is no particular limitation on the (A) low polarity compound, and any conventionally known compound can be used as long as the effects of the present invention are achieved. For example, the (A) low polarity compound is preferably one having a polar component term in the surface free energy of 5 mN / m or less. The (A) low polarity compound has a polar component term in the surface free energy of 4 mN / m or less, more preferably 3 mN / m or less, even more preferably 2.5 mN / m or less, particularly preferably 2 mN / m or less, and most preferably 1.5 mN / m or less. The lower limit is not particularly limited, but is usually 0.05 mN / m, preferably 0.1 mN / m, more preferably 0.15 mN / m, and may be 0.2 mN / m. By using such (A) low polarity compound, it is easy to adjust the polar component term in the surface free energy of the resin layer to a small value.
[0052] As the (A) low polarity compound, a compound having a mold releasing effect, that is, a compound that can be used as a mold releasing agent, can also be preferably used. Examples of the (A) low polarity compound include wax, a long chain alkyl group-containing compound, a fluorine compound, and a silicone compound. Among them, at least one of a wax and a long chain alkyl group-containing compound is preferable, and a wax is more preferable. In the present composition, the (A) low polarity compound may be used alone or in combination of two or more kinds.
[0053] As described above, the uneven structure of the resin layer is preferably formed by phase separation of resins with different compatibility, but by containing component (A) in the composition, a fine uneven structure can be effectively produced by the water- and / or oil-repellent effect of the low-polarity compound (A). The mechanism by which the unevenness is formed by the water- and / or oil-repellent effect is not clear, but it is assumed that the water- and / or oil-repellent effect repels other resins, and the repelled resin forms convex portions, thereby forming fine unevenness more effectively.
[0054] (wax) The wax may include natural wax, synthetic wax, and modified wax. Natural waxes include vegetable waxes, animal waxes, mineral waxes and petroleum waxes. Examples of vegetable waxes include candelilla wax, carnauba wax, rice wax, wood wax, and jojoba oil. Animal waxes include beeswax, lanolin, and spermaceti. Examples of mineral waxes include montan wax, ozokerite, and ceresin. Petroleum waxes include paraffin wax, microcrystalline wax, and petrolatum. Synthetic waxes include synthetic hydrocarbons, modified waxes, hydrogenated waxes, fatty acids, acid amides, amines, imides, ester waxes and ketones.
[0055] Examples of synthetic waxes include Fischer-Tropsch wax (also known as Sasol wax), polyethylene wax, etc. In addition, the following polymers, which are low molecular weight polymers (specifically, polymers with a number average molecular weight of 500 to 20,000), can be mentioned, namely, polypropylene, ethylene-acrylic acid copolymer, polyethylene glycol, polypropylene glycol, and block or graft bond of polyethylene glycol and polypropylene glycol, etc.
[0056] Examples of modified waxes include montan wax derivatives, paraffin wax derivatives, and microcrystalline wax derivatives. The derivatives are compounds obtained by any of the following processes: refining, oxidation, esterification, and saponification, or a combination thereof. Examples of hydrogenated waxes include hydrogenated castor oil and hydrogenated castor oil derivatives.
[0057] Among these, from the viewpoint of excellent performance in forming irregularities by phase separation, the (A) low polarity compound is preferably a synthetic wax, more preferably a polyethylene wax, and even more preferably an oxidized polyethylene wax. When the present composition is diluted with a solvent such as water to prepare a coating liquid, the wax may be dispersed with a surfactant or the like to form a wax emulsion, which may then be blended into the coating liquid.
[0058] From the viewpoints of handling and the ability to form irregularities through phase separation, the number average molecular weight of the synthetic wax is usually in the range of 500 to 30,000, preferably 1,000 to 15,000, and more preferably 2,000 to 8,000. The number average molecular weight is a value measured using gel permeation chromatography (GPC) in terms of polystyrene.
[0059] In addition, taking into consideration that the resin layer is heated for crosslinking or the like when it is formed, the melting point or softening point of the wax is preferably 80° C. or higher, more preferably 110° C. or higher. On the other hand, from the viewpoint of controlling the phase separation performance after the heat treatment, the melting point or softening point is preferably 200° C. or lower, more preferably 170° C. or lower, and even more preferably 150° C. or lower. In particular, when the heat treatment process triggers the phase separation, although it is not certain, it is presumed that the wax melts and the molten wax repels other resins, thereby forming the convex portions. The melting point of the wax can be measured by a differential scanning calorimeter (DSC), and the softening point of the wax can be measured by the method described in JIS K2207:1996.
[0060] (Long-chain alkyl group-containing compounds) The long-chain alkyl group-containing compound refers to a compound having a straight-chain or branched alkyl group having 6 or more carbon atoms, preferably 8 or more, and more preferably 12 or more carbon atoms. Examples of the alkyl group include alkyl groups having about 6 to 30 carbon atoms, such as hexyl, octyl, decyl, lauryl, octadecyl, and behenyl. Examples of compounds having an alkyl group include various long-chain alkyl group-containing polymer compounds, long-chain alkyl group-containing amine compounds, long-chain alkyl group-containing ether compounds, and long-chain alkyl group-containing quaternary ammonium salts. In consideration of heat resistance, polymer compounds are preferred, and from the viewpoint that a small content can effectively obtain unevenness-forming performance due to appropriate phase separation, polymer compounds having a long-chain alkyl group in the side chain are more preferred.
[0061] A polymer compound having a long-chain alkyl group in a side chain can be obtained by reacting a polymer having a reactive group with a compound having an alkyl group capable of reacting with the reactive group. Examples of the reactive group include a hydroxyl group, an amino group, a carboxyl group, and an acid anhydride. Examples of compounds having these reactive groups include polyvinyl alcohol, polyethyleneimine, polyethyleneamine, a polyester resin containing a reactive group, and a poly(meth)acrylic resin containing a reactive group. Among these, polyvinyl alcohol is preferable in consideration of ease of handling. The degree of polymerization of the polyvinyl alcohol used is not particularly limited, but is usually 100 or more, preferably in the range of 300 to 40,000. In addition, the degree of saponification of the polyvinyl alcohol is not particularly limited, but is usually 70 mol% or more, preferably in the range of 70 to 99.9 mol%, more preferably 80 to 97 mol%, and even more preferably 86 to 95 mol%.
[0062] Examples of compounds having an alkyl group capable of reacting with the reactive group include long-chain alkyl group-containing isocyanates such as hexyl isocyanate, octyl isocyanate, decyl isocyanate, lauryl isocyanate, octadecyl isocyanate, behenyl isocyanate, etc., long-chain alkyl group-containing acid chlorides such as hexanoyl chloride, octanoyl chloride, decanoyl chloride, lauroyl chloride, octadecanoyl chloride, behenoyl chloride, etc., long-chain alkyl group-containing amines, long-chain alkyl group-containing alcohols, etc. Among these, in consideration of ease of handling, long-chain alkyl group-containing isocyanates are preferred, and octadecyl isocyanate is particularly preferred.
[0063] Furthermore, polymeric compounds having a long-chain alkyl group in the side chain can also be obtained by polymerization of a long-chain alkyl (meth)acrylate or copolymerization of a long-chain alkyl (meth)acrylate with another vinyl group-containing monomer. Examples of long-chain alkyl (meth)acrylate include hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, octadecyl (meth)acrylate, and behenyl (meth)acrylate.
[0064] (Fluorine compounds) The fluorine compound is a compound containing fluorine atoms in the compound. From the viewpoint of the coating appearance by in-line coating, organic fluorine compounds are preferably used, such as perfluoroalkyl group-containing compounds, polymers of olefin compounds containing fluorine atoms, aromatic fluorine compounds such as fluorobenzene, etc. From the viewpoint of effectively obtaining the unevenness forming performance by moderate phase separation with a small content, it is preferable to use a compound having a perfluoroalkyl group. Furthermore, the fluorine compound can also be a compound containing a long chain alkyl compound as described above.
[0065] Examples of the compound having a perfluoroalkyl group include perfluoroalkyl group-containing (meth)acrylates such as perfluoroalkyl (meth)acrylate, perfluoroalkyl methyl (meth)acrylate, 2-perfluoroalkyl ethyl (meth)acrylate, 3-perfluoroalkyl propyl (meth)acrylate, 3-perfluoroalkyl-1-methylpropyl (meth)acrylate, and 3-perfluoroalkyl-2-propenyl (meth)acrylate, and polymers thereof; and perfluoroalkyl group-containing vinyl ethers such as perfluoroalkyl methyl vinyl ether, 2-perfluoroalkyl ethyl vinyl ether, 3-perfluoropropyl vinyl ether, 3-perfluoroalkyl-1-methylpropyl vinyl ether, and 3-perfluoroalkyl-2-propenyl vinyl ether, and polymers thereof. In consideration of heat resistance, a polymer is preferable. The polymer may be a single compound or a polymer of multiple compounds. In addition, from the viewpoint that a small content can effectively obtain unevenness forming performance due to moderate phase separation, the perfluoroalkyl group preferably has 3 to 11 carbon atoms. Furthermore, it may be a polymer with a compound containing a long-chain alkyl compound as described above, and from the viewpoint of adhesion to the polyester film substrate, a polymer with vinyl chloride is also preferably used.
[0066] (Silicone compounds) The silicone compound is a compound having a silicone structure in the molecule, and examples thereof include silicone emulsion, acrylic grafted silicone, silicone grafted acrylic, amino-modified silicone, perfluoroalkyl-modified silicone, alkyl-modified silicone, etc. In consideration of heat resistance, it is preferable to contain a curable silicone resin. As the type of curable silicone resin, any type of curing reaction such as addition type, condensation type, ultraviolet curing type, electron beam curing type, etc. can be used.
[0067] The content of component (A) in the composition is preferably 5 to 80 mass%, more preferably 10 to 70 mass%, even more preferably 15 to 60 mass%, and even more preferably 20 to 50 mass%, as a ratio of the total non-volatile components in the composition. By making the content equal to or greater than the lower limit, it becomes easy to sufficiently form a concave-convex structure by phase separation. In addition, by making the content equal to or less than the upper limit, it becomes possible to ensure the content of other resins, and it becomes easy to appropriately adjust the concave-convex formation performance by phase separation.
[0068] (((ingredient (B))))) The composition contains a binder resin (B). The component (B) can contribute to the formation of a fine uneven structure due to phase separation, and can also improve the coatability of the present composition when it is made into a coating solution.
[0069] ((Binder resin)) The binder resin selected as the component (B) is a polymer compound having a number average molecular weight (Mn) of 1000 or more as measured by gel permeation chromatography (GPC) in accordance with the "Flow Scheme for the Safety Evaluation of Polymer Compounds" (November 1985, sponsored by the Chemical Substances Council). Among these, those having film-forming properties are preferred. Such a binder resin (B) is not particularly limited, and for example, a conventionally known binder resin can be used. For example, polyester resin, polyurethane resin, (meth)acrylic resin, polyvinyl alcohol, ion-conductive polymer compound, etc. can be mentioned. Among them, from the viewpoint of maintaining the unevenness forming performance by phase separation and forming a coating, it is preferable to use at least one of polyester resin, polyurethane resin, and (meth)acrylic resin. In the present composition, the binder resin may be used alone or in combination of two or more kinds.
[0070] ((Meth)acrylic resin) The (meth)acrylic resin is a polymer made of polymerizable monomers including acrylic and methacrylic monomers. These may be homopolymers or copolymers, or copolymers with polymerizable monomers other than acrylic and methacrylic monomers. The (meth)acrylic polymer is a polymer having a structural unit derived from (meth)acrylic acid or (meth)acrylic acid alkyl esters. The (meth)acrylic polymer may be at least one polymer selected from (meth)acrylic acid and (meth)acrylic acid alkyl esters, or may be a copolymer of at least one selected from these and at least one monomer other than these, such as styrene or a styrene derivative, or a monomer containing a hydroxyl group. Also included are copolymers of these polymers with other polymers (such as polyesters and polyurethanes). For example, block copolymers and graft copolymers. That is, the (meth)acrylic resin may be a (meth)acrylic-modified polyester resin or a (meth)acrylic-modified polyurethane resin. Alternatively, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in a polyester solution or polyester dispersion. Similarly, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in a polyurethane solution or polyurethane dispersion. Similarly, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in another polymer solution or dispersion, and these are also referred to as (meth)acrylic modified polyester resins and (meth)acrylic modified polyurethane resins in this specification. The above-mentioned polyesters and polyurethanes used in the (meth)acrylic resins can be appropriately selected from those exemplified as polyesters and polyurethanes used in the binder resins described later. The (meth)acrylic resin may also contain a hydroxy group or an amino group in order to further improve adhesion to the polyester film.
[0071] The polymerizable monomer is not particularly limited, but particularly representative compounds include various carboxyl group-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; various hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutylhydroxyfumarate, and monobutylhydroxyitaconate; and various hydroxyl group-containing monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, and lauryl (meth)acrylate. Examples of such monomers include various alkyl (meth)acrylic esters; various nitrogen-containing monomers such as (meth)acrylamide, diacetone acrylamide, or (meth)acrylonitrile; nitrogen-containing monomers containing a hydroxyl group such as N-methylol (meth)acrylamide; various styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, and vinyl toluene; various vinyl esters such as vinyl propionate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane; phosphorus-containing vinyl monomers; various vinyl halides such as vinyl chloride and vinylidene chloride; and various conjugated dienes such as butadiene.
[0072] Among the above (meth)acrylic resins, polymers obtained by polymerizing polymerizable monomers including acrylic and methacrylic monomers are preferred, and it is more preferred that the polymerizable monomers include alkyl (meth)acrylic esters. In addition, the present composition containing the (meth)acrylic resin is preferably diluted with a solvent to prepare a coating liquid as described below, and the solvent is preferably water as the main solvent (50 mass% or more). That is, from the viewpoint of facilitating dissolution or dispersion when the coating liquid is made water-based, the polymerizable monomer preferably has a hydrophilic group such as a hydroxyl group or a carboxyl group. In addition, from the viewpoint of effectively obtaining a concave-convex structure by phase separation, it is preferable that the polymerizable monomer has a hydrophilic group such as a hydroxyl group or a carboxyl group. Therefore, the acrylic resin is preferably a polymer obtained by polymerizing an alkyl (meth)acrylic acid ester and a polymerizable monomer including a hydrophilic group-containing monomer such as a monomer containing a hydroxyl group or a monomer containing a carboxyl group. The acrylic resin may also be an emulsion polymer obtained by polymerizing a polymerizable monomer in the presence of a surfactant.
[0073] (Polyvinyl alcohol) Polyvinyl alcohol is a compound having a polyvinyl alcohol moiety, and for example, conventionally known polyvinyl alcohols can be used, including modified compounds in which polyvinyl alcohol is partially acetalized or butyralized. The degree of polymerization of polyvinyl alcohol is not particularly limited, but is usually 100 or more, preferably in the range of 300 to 40,000. When the degree of polymerization is 100 or more, the water resistance of the resin layer is easily improved. In addition, the degree of saponification of polyvinyl alcohol is not particularly limited, but a polyvinyl acetate saponification product having a degree of saponification of 70 mol % or more, preferably in the range of 70 to 99.9 mol %, more preferably 80 to 97 mol %, and even more preferably 86 to 95 mol % is practically used.
[0074] (polyester resin) The polyester resin may be composed of, as main components, for example, the following polyvalent carboxylic acids and polyvalent hydroxy compounds. That is, examples of polyvalent carboxylic acids that can be used include terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfoisophthalic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof. Examples of polyhydric hydroxy compounds include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, sodium dimethylolethylsulfonate, and potassium dimethylolpropionate. One or more of these compounds may be appropriately selected from each of them, and a polyester resin may be synthesized by a conventional polycondensation reaction.
[0075] As a part of the polycarboxylic acid, a product obtained by copolymerizing sulfoisophthalic acids such as 5-sodium sulfoisophthalic acid, introducing sulfonic acid groups into the polyester skeleton, and neutralizing the resulting product to be hydrophilic is preferably used. The amount of copolymerization is usually 1 to 13 mol %, preferably 3 to 10 mol %, and more preferably 5 to 9 mol % based on the total amount of polycarboxylic acid. By introducing an appropriate amount of sulfonic acid groups, the hydrophilicity of the resin can be increased, and the uneven structure can be easily formed. Furthermore, the water dispersion stability can be improved.
[0076] (Ion-conductive polymer compound) The ionically conductive polymer compound is a polymer compound containing an ionically conductive functional group, and examples of such polymer compounds include ammonium group-containing compounds, polyether compounds, sulfonic acid compounds, betaine compounds, etc. Among these, ammonium group-containing compounds are particularly preferred from the viewpoint of high polarity and effective formation of unevenness.
[0077] The ammonium group-containing compound refers to a compound having an ammonium group in the molecule, and is preferably a polymeric compound having an ammonium group. For example, a polymer containing an ammonium group and a monomer having an unsaturated double bond as a component can be used.
[0078] Specific examples of such polymers include polymers having a repeating unit that is a component represented by the following formula (1): These may be homopolymers or copolymers, or may be copolymers of a plurality of other components.
[0079] [ka]
[0080] In the above formula (1), R 1 , R 2 are each independently a hydrogen atom, an alkyl group, a phenyl group, or the like, and these alkyl groups and phenyl groups may be substituted with the groups shown below. Examples of the substitutable groups include a hydroxyl group, an amide group, an ester group, an alkoxy group, a phenoxy group, a naphthoxy group, a thioalkoxy group, a thiophenoxy group, a cycloalkyl group, a trialkylammonium alkyl group, a cyano group, and halogens. 1 and R 2 may be chemically bonded, for example, -(CH2) m Examples include -(m = an integer of 2 to 5), -CH(CH3)CH(CH3)-, -CH=CH-CH=CH-, -CH=CH-CH=N-, -CH=CH-N=C-, -CH2OCH2-, -(CH2)2O(CH2)2-, and the like.
[0081] X in the above formula (1) - can be appropriately selected within the scope not impairing the gist of the present invention. Examples include halogen ions, sulfonates, phosphates, nitrates, alkylsulfonates, and carboxylates.
[0082] Among the above-mentioned polymers, i.e., polymers containing a monomer having an ammonium group and an unsaturated double bond as a component, from the viewpoint of improving film-forming properties and obtaining a stable coating, the polymers may be copolymerized with other monomers. Examples of other monomers include alkyl acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, and butyl acrylate; alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate; and acrylamides such as n-methylolacrylamide.
[0083] From the viewpoint of further increasing polarity and effectively forming unevenness, a homopolymer having the constituent element represented by the above formula (1) as a repeating unit is preferred.
[0084] The number average molecular weight of the ammonium group-containing compound is preferably 1000 to 500000, more preferably 2000 to 350000, and even more preferably 5000 to 200000. By making the molecular weight equal to or greater than the lower limit, the strength of the coating film can be prevented from being weakened, and the heat resistance stability can be easily improved. By making the molecular weight equal to or less than the upper limit, the viscosity of the coating liquid can be prevented from being increased, and the handling and coating properties can be easily improved.
[0085] (Polyurethane resin) The polyurethane resin is a polymeric compound having a urethane bond in the molecule, and is preferably water-dispersible or water-soluble. In the present invention, the polyurethane resin may be used alone or in combination of two or more kinds.
[0086] In order to impart water dispersibility or water solubility, it is common and preferable to introduce hydrophilic groups such as hydroxyl groups, carboxyl groups, sulfonic acid groups, sulfonyl groups, phosphoric acid groups, ether groups, etc., into the polyurethane resin. Among the hydrophilic groups, carboxyl groups and sulfonic acid groups are particularly preferable from the viewpoint of adhesion between the resin layer and the polyester film.
[0087] One method for producing polyurethane resin is by reacting a hydroxyl group-containing compound with an isocyanate. As the hydroxyl group-containing compound used as a raw material, polyol is preferably used, for example, polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, and acrylic polyols. These compounds may be used alone or in combination.
[0088] Examples of polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol.
[0089] Examples of polyester polyols include those obtained by reacting polyvalent carboxylic acids or their acid anhydrides with polyhydric alcohols. Examples of polyvalent carboxylic acids include malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, and isophthalic acid. Examples of polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-methyl-2-propyl-1,3-propanediol, 1,5-hexanediol ... ,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamines, lactonediols, and the like.
[0090] Examples of polycarbonate-based polyols include polycarbonate diols obtained by dealcoholization reaction of polyhydric alcohols with dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, etc., such as poly(1,6-hexylene) carbonate and poly(3-methyl-1,5-pentylene) carbonate. Among the above, polyester polyols are preferred.
[0091] Examples of polyisocyanate compounds used to obtain polyurethane resins include aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and tolidine diisocyanate; aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethyl xylylene diisocyanate; aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidenedicyclohexyl diisocyanate. These may be used alone or in combination.
[0092] A chain extender may be used when synthesizing the polyurethane resin. The chain extender is not particularly limited as long as it has two or more active groups that react with an isocyanate group, and generally, a chain extender having two hydroxyl groups or two amino groups can be mainly used.
[0093] Examples of chain extenders having two hydroxyl groups include glycols such as aliphatic glycols, such as ethylene glycol, propylene glycol, and butanediol; aromatic glycols, such as xylylene glycol and bishydroxyethoxybenzene; and ester glycols, such as neopentyl glycol hydroxypivalate.
[0094] Examples of chain extenders having two amino groups include aromatic diamines such as tolylenediamine, xylylenediamine, and diphenylmethanediamine; aliphatic diamines such as ethylenediamine, propanediamine, hexanediamine, 2,2-dimethyl-1,3-propanediamine, 2-methyl-1,5-pentanediamine, trimethylhexanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine; and alicyclic diamines such as 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, dicyclohexylmethanediamine, 1,4-diaminocyclohexane, and 1,3-bisaminomethylcyclohexane.
[0095] (((ingredient (C)))) (C) The crosslinking agent is not particularly limited, and a conventionally known crosslinking agent can be used. By using the crosslinking agent, the resin layer can be easily made into a cured resin layer. Examples of the crosslinking agent include a melamine compound, an oxazoline compound, an epoxy compound, a carbodiimide compound, an isocyanate compound, and a silane coupling compound. Among them, from the viewpoint of ease of adjusting the unevenness forming performance by phase separation, it is preferable to use at least one of a melamine compound and an oxazoline compound as the crosslinking agent, and it is more preferable to use a melamine compound. In the present composition, the crosslinking agent may be used alone or in combination of two or more kinds.
[0096] (Melamine compounds) The melamine compound refers to a compound having a melamine skeleton in the compound, and for example, alkylolated melamine derivatives, compounds obtained by reacting an alkylolated melamine derivative with an alcohol to partially or completely etherify the same, and mixtures thereof can be used. Examples of alkylolation include methylolation, ethylolation, isopropylolation, n-butylolation, isobutyrolation, etc. Among these, methylolation is preferred from the viewpoint of reactivity. As the alcohol used in the etherification, methanol, ethanol, isopropanol, n-butanol, isobutanol, etc. are preferably used, and among these, methanol is more preferred. The melamine compound may be either a monomer or a dimer or higher polymer, or a mixture of these may be used. Furthermore, a product obtained by co-condensing melamine with urea or the like may also be used, and a catalyst may also be used in the present composition to increase the reactivity of the melamine compound.
[0097] (Oxazoline compounds) The oxazoline compound is a compound having an oxazoline group in the molecule, and in particular, a polymer containing an oxazoline group is preferred, and can be prepared by polymerization of an addition polymerizable oxazoline group-containing monomer alone or with other monomers. Examples of the addition polymerizable oxazoline group-containing monomer include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline, and one or a mixture of two or more of these can be used. Among these, 2-isopropenyl-2-oxazoline is suitable because it is easily available industrially. The other monomer is not limited as long as it is a monomer that can be copolymerized with the addition-polymerizable oxazoline group-containing monomer, and examples thereof include (meth)acrylic acid esters such as alkyl (meth)acrylates (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrenesulfonic acid, and salts thereof (sodium salts, potassium salts, ammonium salts, tertiary amine salts, etc.); unsaturated nitriles such as acrylonitrile and methacrylonitrile; (meth)acrylamide, N-alkyl (meth)acrylate, etc. Examples of the monomer include unsaturated amides such as t)acrylamide and N,N-dialkyl(meth)acrylamide (the alkyl group can be a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, a 2-ethylhexyl group, a cyclohexyl group, and the like); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride and vinylidene chloride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. One or more of these monomers can be used. The oxazoline compound may have a polyalkylene oxide chain such as a polyethylene oxide chain, and for example, a (meth)acrylate having a polyalkylene oxide chain may be used as another monomer. From the viewpoint of improving the adhesion of the resin layer to the polyester film, the amount of oxazoline groups in the oxazoline compound is preferably in the range of 0.5 to 10 mmol / g, more preferably 1 to 9 mmol / g, and further preferably 3 to 8 mmol / g.
[0098] (Epoxy compounds) The epoxy compound is a compound having an epoxy group in the molecule, and examples thereof include condensations of epichlorohydrin, ethylene glycol, polyethylene glycol, glycerin, polyglycerin, bisphenol A, etc. with a hydroxyl group or an amino group, polyepoxy compounds, diepoxy compounds, monoepoxy compounds, and glycidylamine compounds. Examples of the polyepoxy compound include sorbitol polyglycidyl ether, polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, and trimethylolpropane polyglycidyl ether. Examples of diepoxy compounds include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether. Examples of the monoepoxy compound include allyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether, and examples of the glycidylamine compound include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylamino)cyclohexane, etc. From the viewpoint of improving the adhesion of the resin layer to the polyester film, polyether-based epoxy compounds are preferred. In terms of the amount of epoxy groups, a polyepoxy compound having three or more functional groups is more preferable than a difunctional compound.
[0099] (Carbodiimide compounds) A carbodiimide compound is a compound having a carbodiimide structure, i.e., a compound having one or more carbodiimide structures in its molecule. However, for better adhesion between the resin layer and the polyester film, a polycarbodiimide compound having two or more carbodiimide structures in its molecule is more preferred.
[0100] Carbodiimide compounds can be synthesized by conventionally known techniques, and generally, condensation reaction of diisocyanate compounds is used. The diisocyanate compounds are not particularly limited, and both aromatic and aliphatic compounds can be used, and specific examples include tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate.
[0101] The content of the carbodiimide group contained in the carbodiimide compound, in terms of carbodiimide equivalent (weight [g] of the carbodiimide compound for providing 1 mol of carbodiimide group), is usually in the range of 100 to 1000, preferably 250 to 800, and more preferably 300 to 700. By using within the above range, the durability of the resin layer is improved.
[0102] Furthermore, within the scope of the present invention, in order to improve the water solubility or water dispersibility of the polycarbodiimide compound, a surfactant may be added, or a hydrophilic monomer such as a polyalkylene oxide, a quaternary ammonium salt of a dialkylamino alcohol, or a hydroxyalkylsulfonate may be added.
[0103] (Isocyanate compounds) The isocyanate compound is a compound having an isocyanate or an isocyanate derivative structure, such as a blocked isocyanate. Examples of the isocyanate include aromatic isocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic isocyanates having an aromatic ring, such as α,α,α',α'-tetramethyl xylylene diisocyanate; aliphatic isocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic isocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isopropylidenedicyclohexyl diisocyanate. In addition, polymers and derivatives such as biuretized products, isocyanurate products, uretdione products, and carbodiimide modified products of these isocyanates are also included. These may be used alone or in combination. Among the above isocyanates, aliphatic isocyanates or alicyclic isocyanates are more preferable than aromatic isocyanates in order to prevent yellowing due to ultraviolet rays.
[0104] When used in the form of a blocked isocyanate, examples of the blocking agent include bisulfites; phenolic compounds such as phenol, cresol, and ethylphenol; alcohol compounds such as propylene glycol monomethyl ether, ethylene glycol, benzyl alcohol, methanol, and ethanol; active methylene compounds such as methyl isobutanoylacetate, dimethyl malonate, diethyl malonate, methyl acetoacetate, ethyl acetoacetate, and acetylacetone; mercaptan compounds such as butyl mercaptan and dodecyl mercaptan; lactam compounds such as ε-caprolactam and δ-valerolactam; amine compounds such as diphenylaniline, aniline, and ethyleneimine; acid amide compounds such as acetanilide and acetic acid amide; and oxime compounds such as formaldehyde oxime, acetaldoxime, acetone oxime, methyl ethyl ketone oxime, and cyclohexanone oxime, which may be used alone or in combination of two or more.
[0105] The isocyanate compound may be used alone or as a mixture or bond with various polymers. In terms of improving the dispersibility and crosslinking property of the isocyanate compound, it is preferable to use a mixture or bond with a polyester resin or a polyurethane resin.
[0106] (Silane coupling compound) A silane coupling compound is an organosilicon compound that has an organic functional group and a hydrolyzable group such as an alkoxy group in one molecule. For example, epoxy group-containing compounds such as 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; vinyl group-containing compounds such as vinyltrimethoxysilane and vinyltriethoxysilane; styryl group-containing compounds such as p-styryltrimethoxysilane and p-styryltriethoxysilane; (meth)acrylic group-containing compounds such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane; 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3 -aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane and other amino group-containing compounds; tris(trimethoxysilylpropyl)isocyanurate, tris(triethoxysilylpropyl)isocyanurate and other isocyanurate group-containing compounds; 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane and other mercapto group-containing compounds.
[0107] The total content of component (B) and component (C) in the composition is preferably 5 to 95% by mass, more preferably 10 to 80% by mass, even more preferably 20 to 70% by mass, and even more preferably 30 to 60% by mass, as a percentage of the total non-volatile components in the composition. By setting the content to the above lower limit or more, it becomes easy to achieve both the formation of a concave-convex structure by phase separation and the improvement of the coatability when the composition is used as a coating liquid. In addition, by setting the content to the above upper limit or less, the content of one of the resins can be secured, and it becomes easy to appropriately adjust the concave-convex formation performance by phase separation. The content of component (B) in the composition is preferably 5 to 50 mass%, more preferably 8 to 45 mass%, even more preferably 10 to 40 mass%, and even more preferably 13 to 36 mass%, as a ratio of the total non-volatile components in the composition. By making the content equal to or greater than the lower limit, it becomes easy to achieve both the formation of a concave-convex structure by phase separation and the improvement of the coatability when the composition is used as a coating liquid. In addition, by making the content equal to or less than the upper limit, it becomes possible to ensure the content of one of the resins, and it becomes easy to appropriately adjust the concave-convex formation performance by phase separation. The content of component (C) in the composition is preferably 5 to 50 mass%, more preferably 8 to 40 mass%, even more preferably 10 to 35 mass%, and even more preferably 15 to 40 mass%, as a ratio of the total non-volatile components in the composition. By making the content equal to or greater than the lower limit, it becomes easy to achieve both the formation of a concave-convex structure by phase separation and the improvement of the coating strength. In addition, by making the content equal to or less than the upper limit, it becomes possible to ensure the content of one of the resins, and it becomes easy to appropriately adjust the concave-convex formation performance by phase separation.
[0108] (((particularly preferred form))) As components (A) and (B) contained in the present composition, combinations of (a) a low-polarity compound and a binder resin, (b) a low-polarity compound and a crosslinking agent, and (c) a low-polarity compound, a binder resin, and a crosslinking agent are particularly preferred, and combination (c) is particularly preferred.
[0109] (((ingredient(D)))) When the composition contains the (C) crosslinking agent, it may further contain (D) a crosslinking catalyst (component (D)). The (D) crosslinking catalyst is used to enhance the reactivity of the crosslinking agent, and various known catalysts can be used. For example, amine compounds, salts of amine compounds, organic acids such as aromatic sulfonic acid compounds such as p-toluenesulfonic acid and phosphoric acid compounds and their salts, imine compounds, amidine compounds, guanidine compounds, organometallic compounds, and metal salts such as zinc stearate, zinc myristate, aluminum stearate, and calcium stearate are listed. Among these, amine compounds, salts of amine compounds, and p-toluenesulfonic acid are preferred, and amine compounds and salts of amine compounds are more preferred.
[0110] When the composition contains a crosslinking catalyst, the content of the crosslinking catalyst (component (D)) in the composition is preferably 0.01 to 5 mass%, more preferably 0.1 to 4 mass%, and even more preferably 1 to 3 mass%, as a ratio of the total non-volatile components in the composition. By setting the content in this range, it becomes easy to suppress a decrease in pot life, and it also becomes easy to impart the ability to form unevenness by phase separation.
[0111] (((ingredient(E))))) The present composition may contain (E) particles (component (E)). By using particles in combination, it becomes easy to further improve the surface hardness of the convex parts in the resin layer having a concave-convex structure. In addition, by increasing the surface hardness of the convex parts, the convex parts on the resin layer surface are less likely to deform when the present laminated polyester film is rolled, making it easier to obtain a good roll appearance. In particular, when the present composition is composed only of resin, the convex parts are soft, so that when the film is rolled, the convex parts deform and the air passage is crushed, and the inherent excellent handleability may not be fully exhibited. Therefore, there are some embodiments in which it is preferable to contain particles.
[0112] Examples of the (E) particles include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, as well as organic particles such as crosslinked polymers such as crosslinked silicone resin particles, crosslinked acrylic resin particles, crosslinked styrene-acrylic resin particles, and crosslinked polyester particles, calcium oxalate, and ion exchange resins. Of these, silica and aluminum oxide are preferred.
[0113] The average particle size of the (E) particles is preferably 0.5 to 300 nm, more preferably 1 to 250 nm, even more preferably 2 to 200 nm, even more preferably 2.5 to 200 nm, even more preferably 3 to 150 nm, even more preferably 3.5 to 100 nm, even more preferably 4 to 60 nm, and even more preferably 4.5 to 30 nm. If the average particle size is within this range, the generation of coarse protrusions due to particle aggregation and contamination of the process due to particle dropout can be suppressed, making it easier to obtain the desired fine uneven structure. The average particle size can be measured by a method that is more suitable for the average particle size, including a method of calculating the particle size from the specific surface area measured by a specific surface area measuring device and the particle density, a method of calculating the particle diameter by observing with a transmission electron microscope (TEM) or a scanning electron microscope (SEM), and a method of determining the particle diameter by measurement using dynamic light scattering.
[0114] When the composition contains (E) particles, the content of (E) particles in the composition is preferably 1 to 50 mass%, more preferably 10 to 48 mass%, even more preferably 15 to 45 mass%, and even more preferably 22 to 43 mass%, as a ratio of the total non-volatile components in the composition. By setting the content in this range, it becomes easy to obtain a desired fine uneven structure while improving the surface hardness of the convex parts.
[0115] (((Other ingredients))) In addition to the above-mentioned components, additives such as antifoaming agents, coatability improvers, surfactants, thickeners, organic lubricants, ultraviolet absorbers, antioxidants, foaming agents, dyes, and pigments may be appropriately added within the scope of the present invention.
[0116] (((solvent))) The present composition may be diluted with a solvent to form a coating liquid, that is, the present composition may be applied as a liquid coating liquid to, for example, the present polyester film, and then dried and cured as necessary to form a resin layer. Each of the components constituting the present composition (components (A), (B), (C), and optionally added (D) crosslinking catalyst and (E) particles, other components, etc.) may be dissolved or dispersed in a solvent. When the composition is used as a coating solution, the concentration of the total non-volatile components of the composition in the coating solution is preferably 0.1 to 50% by mass. If the concentration is equal to or higher than the lower limit, a resin layer of a desired thickness can be efficiently formed. On the other hand, if the concentration is equal to or lower than the upper limit, the viscosity during coating can be suppressed, thereby improving the appearance of the resin layer and increasing the stability in the coating solution.
[0117] The solvent is not particularly limited, and either water or an organic solvent can be used. From the viewpoint of environmental protection, it is preferable to prepare an aqueous coating liquid using water as the main solvent (50% by mass or more of the total solvent). The water content is preferably 60% by mass or more, more preferably 70% by mass or more. The aqueous coating liquid may contain a small amount of an organic solvent. The specific amount of the organic solvent is preferably equal to or less than the amount of water on a mass basis, for example, 50% by mass or less, preferably 40% by mass or less, more preferably 30% by mass or less of the solvent. Examples of organic solvents to be used in combination with water include alcohols such as ethanol, isopropanol, ethylene glycol, and glycerin; ethers such as ethyl cellosolve, t-butyl cellosolve, propylene glycol monomethyl ether, and tetrahydrofuran; ketones such as acetone and methyl ethyl ketone; esters such as ethyl acetate; amines such as dimethylethanolamine, etc. These can be used alone or in combination. By appropriately selecting and incorporating these organic solvents into the aqueous coating solution as needed, the stability and coatability of the coating solution may be improved.
[0118] When only an organic solvent is used as the above solvent, examples of such organic solvents include aromatic hydrocarbons such as toluene; aliphatic hydrocarbons such as hexane, heptane, and isooctane; esters such as ethyl acetate and butyl acetate; ketones such as ethyl methyl ketone and isobutyl methyl ketone; alcohols such as ethanol and 2-propanol; ethers such as diisopropyl ether and dibutyl ether, etc. These may be used alone or in combination of multiple types, taking into account solubility, coatability, boiling point, etc.
[0119] It can be presumed that unreacted substances, post-reaction compounds, or mixtures thereof of each component (component (A) and (B), optionally added (C) crosslinking agent, (D) crosslinking catalyst, and (E) particles, other components, etc.) constituting the present composition are present in the resin layer. Analysis of each component in the resin layer can be performed, for example, by TOF-SIMS, ESCA, fluorescent X-ray, etc.
[0120] <Hansen solubility parameter> Each component (component (A), (B), and (C)) constituting the present composition can also be explained by the Hansen solubility parameter (HSP). More specifically, the uneven structure of the present resin layer is a fine shape formed by phase separation as described above, and this phase separation can be explained using HSP.
[0121] Hansen solubility parameter (HSP) is an index that indicates the degree to which a substance dissolves in another substance. HSP is a three-dimensional representation of the solubility parameter introduced by Hildebrand, which is divided into three components: dispersion term δd, polar term δp, and hydrogen bond term δh.
[0122] The dispersion term δd indicates the effect due to dispersion forces, the polar term δp indicates the effect due to dipole-dipole forces, and the hydrogen bond term δh indicates the effect due to hydrogen bonding forces, and are expressed as follows: The units are MPa. 0.5 It is. δd: Energy derived from intermolecular dispersion forces δp: Energy derived from intermolecular polar forces δh: Energy derived from hydrogen bonding forces between molecules
[0123] The definition and calculation of HSP are described in the following literature. Charles M. Hansen, Hansen Solubility Parameters: A Users Handbook (CRC Press, 2007).
[0124] The dispersion term reflects the London dispersion force, the polar term reflects the dipole moment, and the hydrogen bond term reflects the effects of water, alcohol, etc.
[0125] Furthermore, molecules with similar HSP vectors can be judged to have high solubility, and the similarity of the vectors can be determined by the HSP distance (HSP distance).
[0126] In the present invention, the HSP [δd, δp, δh] of a resin (corresponding to components (A), (B), and (C) as described above) can be calculated by evaluating the solubility in various solvents with known HSP, and calculating the interaction sphere and its center, the HSP, by defining solvents in which the resin dissolves as good solvents and solvents in which the resin is insoluble or swells as poor solvents. For the calculation, for example, commercially available Hansen Solubility Parameter calculation software HSPiP (Hansen Solubility Parameters in Practice) can be used, and the thresholds for good and poor solvents can be determined so that the fitting value of the calculated interaction sphere is closest to 1. For accurate measurement, it is preferable that the solvents used for the measurement each have various HSPs [δD, δP, δH], and specific types of solvents are as shown in Table 1. According to Table 1, a solubility test is performed with 18 or more types of solvents, and a judgment is made as to whether the solvent type is a good solvent or a poor solvent. In the table, "≧1" means that the measurement is performed for one or more types of solvents, and "≧2" means that the measurement is performed for two or more types of solvents.
[0127] [Table 1]
[0128] Furthermore, if the chemical structure of a resin is clear, the HSP [δd, δp, δh] can be calculated using the Y-MB (Yamamoto Molecular Break) function of HSPiP. If the chemical structure is not clear, it can be determined by actual measurement using conventionally known methods.
[0129] In addition, the formed resin layer can be dissolved in a suitable solvent, and each component can be separated, and then the HSP of the resin in the resin layer can be determined using the same method as above.
[0130] It is preferable that the components (A), (B), and (C) include at least one selected from the component (A) and at least one selected from the components (B) and (C) satisfy the relationship of the following formula (2). HSP distance={4×(δd1-δd2) 2 +(δp1-δp2) 2 +(δh1-δh2) 2} 0.5 ≧5.0 (2) Here, δd1, δp1, and δh1 represent δd, δp, and δh of component (A) in the Hansen solubility parameters [δd, δp, δh], respectively, and δd2, δp2, and δh2 represent δd, δp, and δh of component (B) or (C), respectively. Note that δp1≦δp2.
[0131] The HSP distance defined by the above formula (2) is 5 or more, preferably 6 or more, more preferably 7 or more, and even more preferably 8 or more. If the HSP distance is within this range, a composition consisting of resins with different compatibility is more likely to undergo phase separation, and even if the resin layer is a thin film, it can have a desired fine uneven structure. The HSP distance defined by the above formula (2) is not particularly limited, but is preferably 25 or less, more preferably 23 or less, even more preferably 21 or less, even more preferably 18 or less, and even more preferably 15 or less.
[0132] In order to be said to satisfy the relationship of the above formula (2), the components (resins) used as components (A), (B), and (C) are not particularly limited, and it is sufficient that the two resins in at least one combination among the possible combinations when two resins are selected, one for each component, satisfy the relationship of the above formula (2). For example, if the component (A) contained in this composition is two types, resin A-1 and resin A-2, and the component (B) contained in this composition is two types, resin B-1 and resin B-2, the possible combinations when selecting two types of resins based on the components (A) and (B) are resin A-1 and resin B-1, resin A-1 and resin B-2, resin A-2 and resin B-1, and resin A-2 and resin B-2. Therefore, what is meant by the above is that at least one of the four combinations should satisfy the relationship of the above formula (2). In other words, it is sufficient that the combination in which the HSP distance between two types of resin is the longest among the above four combinations (the longest distance between the two types of resin) satisfies the relationship of the above formula (2).
[0133] Next, the HSPs of the components (A), (B) and (C) exemplified above will be described respectively.
[0134] (((HSP of component (A))) From the viewpoint of forming a fine uneven structure by phase separation, the polarity term δp1 of the component (A) is 9 MPa 0.5 It is preferably equal to or less than 8 MPa, and more preferably 0.5 Less than 7MPa, more preferably 0.5 If the value of the polarity term Δp1 is within this range, the polarity of component (A) can be reduced, making it easier to satisfy the relationship of formula (2) above, and as a result, making it easier to form a desired uneven structure. The value of the polarity term Δp1 of component (A) is not particularly limited, but is preferably 1 MPa. 0.5 More preferably, 2MPa 0.5 More preferably, 3 MPa 0.5 More preferably, 4 MPa 0.5 The polarity term δp1 of the component (A) is usually equal to or less than the polarity term δp2 of the component (B). In addition, the hydrogen bond term δh1 of component (A) is 15 MPa. 0.5 It is preferable that the pressure is equal to or less than 12MPa. 0.5 Less than 9MPa, more preferably 0.5 On the other hand, the hydrogen bond term δh1 of component (A) is 1 MPa. 0.5 It is preferable that the pressure is equal to or higher than 3 MPa, and more preferable that the pressure is equal to or higher than 3 MPa. 0.5 More preferably, 5 MPa 0.5 When the content is equal to or more than the above lower limit, it is possible to prevent the hydrogen bond term of component (A) from becoming too low, and therefore it is possible to prevent the interaction with component (B) from becoming weak, which leads to layer separation and thus prevents the formation of an uneven shape. The dispersion term δd1 of the component (A) is not particularly limited, but is preferably 6 MPa 0.5 It is preferable that the pressure is equal to or higher than 8MPa, and more preferable that the pressure is equal to or higher than 8MPa. 0.5 More preferably, 10 MPa 0.5 The upper limit is not particularly limited, but is preferably 25 MPa. 0.5 , more preferably 23 MPa 0.5, more preferably 20 MPa 0.5 It is. When the value of the hydrogen bond term Δh1 and / or the dispersion term Δd1 is within this range, the relationship of the above formula (2) is easily satisfied. In addition, when the present composition contains two or more kinds of components (A), at least one of the components (A) may have the above-mentioned value of the polar term δp1, but all of the components (A) may have the above-mentioned value of the polar term δp1. The same applies to the hydrogen bond term δh1 and the dispersion term δd1.
[0135] (((HSP of component (B) or (C))) The hydrogen bond term δh2 of component (B) or (C) can contribute to the formation of a fine uneven structure by phase separation, and from the viewpoint of improving the coatability when the composition is used as a coating liquid, is 5.5 MPa. 0.5 It is preferable that the pressure is 6.5MPa or more. 0.5 More preferably, it is 7.5 MPa or more. 0.5 More preferably, it is equal to or higher than 8 MPa. 0.5 More preferably, 9 MPa or more 0.5 That's all. If the value of the hydrogen bond term Δh2 is within this range, the hydrophilicity of component (B) can be increased, and the coatability can be improved. In addition, it becomes easier to satisfy the relationship (2) above, and as a result, it becomes easier to form the desired uneven structure. In addition, the hydrogen bond term δh2 of component (B) is 25 MPa. 0.5 It is preferable that the pressure is less than 23MPa. 0.5 Less than 20.3MPa is more preferable. 0.5 By setting the value of the hydrogen bond term δh2 to a certain value or less, the hydrophilicity does not become too high, which prevents the coating film from absorbing water and becoming soft, thereby preventing a decrease in unevenness strength, and making it easier to improve slipperiness. In addition, the polarity term δp2 of component (B) or (C) is 7 MPa. 0.5 It is preferable that the pressure is equal to or higher than 8MPa, and more preferable that the pressure is equal to or higher than 8MPa. 0.5 More preferably, 9 MPa 0.5 The dispersion term δd2 is not particularly limited, but is 6 MPa 0.5It is preferable that the pressure is equal to or higher than 8MPa, and more preferable that the pressure is equal to or higher than 8MPa. 0.5 More preferably, 10 MPa 0.5 That is all. If the value of the hydrogen bond term Δh2 and / or the dispersion term Δd2 is within this range, the relationship of the above formula (2) is easily satisfied. In addition, when the present composition contains two or more kinds of components (B) or (C), it is sufficient that at least one of the components (B) has the above-mentioned value of the hydrogen bond term δh2, but all of the components (B) or (C) may have the above-mentioned value of the hydrogen bond term δh2. The same applies to the polar term δp2 and the dispersion term δd2.
[0136] The resin layer must contain at least two resins, one selected from component (A) and one selected from component (B) or (C), but it is preferable to contain three or more resins in order to make it easier to adjust the uneven shape and to control the adhesion to the polyester film and the coating strength. In that case, it is preferable to consider the distance to the third component resin in addition to the longest distance between the two resins. The third component resin may be selected from component (A), component (B) or (C), or other components, but is preferably selected from at least component (B). In a more preferred embodiment, the polarity term δp1 of the component (A) is 9 MPa. 0.5 In addition to satisfying the above, when the component (A) contains a resin whose HSP distance is 19 or more, the component (A) may contain a resin whose HSP distance is 15 or less. In this case, the HSP distance is calculated by the relational expression defined in the above formula (2). If the above condition can be satisfied, a fine uneven structure can be more effectively expressed by phase separation. From this viewpoint, it is preferable that the polarity term Δp1 is 9 MPa. 0.5 It is more preferable that the composition contains a resin having an HSP distance of 7 or more relative to component (A), which is the following: It more preferably contains a resin having an HSP distance of 8 or more. If the composition contains a resin having an HSP distance of 19 or more, it is more preferable that the composition further contains a resin having an HSP distance of 15 or less, and more preferably contains a resin having an HSP distance of 13 or less.
[0137] <Method of forming resin layer> Next, a method for forming the resin layer constituting the present laminated polyester film will be described. The present resin layer may be formed by applying the present composition to a polyester film and, if necessary, subjecting the applied composition to treatments such as drying, curing, heat treatment, etc., and it is preferable to at least perform heat treatment. The method for applying the resin composition is not particularly limited, and any conventionally known coating method such as reverse gravure coating, direct gravure coating, roll coating, die coating, bar coating, curtain coating, etc. may be used.
[0138] The resin layer can be formed by in-line coating or off-line coating. The method of heat-treating the applied resin composition is not particularly limited, and when the resin layer is formed by off-line coating, the heat treatment is usually performed at 80 to 200°C for 3 to 40 seconds, preferably at 100 to 180°C for 3 to 40 seconds. On the other hand, when the resin layer is formed by in-line coating, the heat treatment is usually performed at 70 to 280°C for 3 to 200 seconds. The heat treatment may be performed in two or more steps at different temperatures within the above temperature range. At least a part of the heat treatment may be performed by heating during stretching. Drying and curing may be performed together by heating in the heat treatment.
[0139] In the present invention, the resin layer is preferably formed by in-line coating, which is a method for treating the surface of a polyester film during the film-forming process. In-line coating is a method of coating within the polyester film production process, specifically, coating at any stage from melt extrusion of polyester to stretching, heat setting and winding up. Usually, coating is performed on any of the following: an unstretched sheet obtained by melting and quenching, a stretched uniaxially stretched film, a biaxially stretched film before heat setting, or a film after heat setting and before winding up.
[0140] Although not limited to the following, for example, in the case of sequential biaxial stretching, a method in which a uniaxially stretched film stretched in the longitudinal direction (machine direction) is coated and then stretched in the transverse direction is particularly advantageous. According to such a method, film formation and resin layer formation can be carried out simultaneously, which is advantageous in terms of production costs, and since stretching is carried out after coating, the thickness of the resin layer can be changed by the stretching ratio, and thin film coating can be carried out more easily than with off-line coating films.
[0141] Furthermore, by providing a resin layer on the film before stretching, the resin layer can be stretched together with the polyester film, and this allows the resin layer to be firmly attached to the polyester film.
[0142] Furthermore, in the production of biaxially stretched polyester film, the film can be stretched while holding the ends with clips or the like, thereby restraining the film in both the vertical and horizontal directions. This allows the film to be subjected to high temperatures in the subsequent heat treatment (heat fixing process) without wrinkles or the like being formed and while maintaining its flatness. Therefore, the heat treatment performed after coating can be performed at a high temperature that cannot be achieved by other methods, so that the film-forming property of the resin layer is improved and the resin layer and the polyester film can be more firmly adhered to each other. Furthermore, a strong resin layer can be formed, and the performance such as migration resistance and moist heat resistance of various functional layers that can be formed on the resin layer can be improved.
[0143] Regardless of whether off-line coating or in-line coating is used, heat treatment and irradiation with active energy rays such as ultraviolet rays may be used in combination as necessary. The polyester film constituting the present laminated polyester film may be previously subjected to a surface treatment such as a corona treatment or a plasma treatment.
[0144] The coating amount of the non-volatile component of the present resin layer is preferably 0.005 to 0.95 g / m 2 , more preferably 0.01 to 0.5 g / m 2 , and more preferably 0.02 to 0.2 g / m2 When the coating amount is within this range, a fine uneven structure can be formed by phase separation. The coating amount can be calculated from the concentration of non-volatile components in the coating solution, the coating amount before drying derived from the consumption amount of the coating solution, the transverse stretching ratio, and the like. The coating amount of the non-volatile component refers to the coating amount in the present laminated polyester film, and for example, in the case where drying and stretching are performed, it refers to the coating amount after drying and stretching.
[0145] <<<Physical properties of laminated polyester film>>> The load length ratio (Rmr(90)) of the roughness curve at a cutting level of 90% on the resin layer surface of the present laminated polyester film is 95% or less.
[0146] The load length ratio (Rmr(c)) is one of the line roughness parameters (JIS B 0601:2013) and represents the ratio of the load length ML(c) of the profile curve element at the cutting level c (height %) or μm to the evaluation length Ln, and is calculated by the following formula (3).
[0147]
number
[0148] Here, the inventors considered that the load length ratio (Rmr(90)) is effective as an index representing the unevenness distribution of the uneven structure. For example, a film with a large concave distribution has a small load length ratio (Rmr(90)) value, and a film with a large convex distribution has a large load length ratio (Rmr(90)) value. If the load length ratio (Rmr(90)) is small, the gaps between the films when the film is wound into a roll are large, which improves the ease of air escape and improves winding properties. The load length ratio (Rmr(90)) of the roughness curve at the cutting level of 90% is 95% or less, as described above, preferably 90% or less, and more preferably 85% or less. The lower limit is not particularly limited, and is about 1%, preferably 10%, and more preferably 20%. The load length ratio (Rmr(90)) can be adjusted by the composition and content in the composition.
[0149] The arithmetic mean roughness (Ra) of the resin layer surface is preferably 15 nm or more, more preferably 20 nm or more, even more preferably 30 nm or more, and particularly preferably 35 nm or more. The upper limit is not particularly limited, but is preferably 600 nm, more preferably 400 nm, and even more preferably 200 nm. If the arithmetic mean roughness (Ra) is equal to or greater than the lower limit, the resin layer has a fine uneven structure, and the laminated polyester film has good handleability. If the arithmetic mean roughness (Ra) is equal to or less than the upper limit, the uneven structure of the resin layer has a sufficiently fine shape.
[0150] The arithmetic mean roughness (Ra) is one of the line roughness parameters (JIS B 0601:2013) and represents the average height difference from the average surface. That is, when a portion of the reference length L is sampled, the average line of this sampled portion is taken as the x-axis, the direction of the longitudinal magnification is taken as the y-axis, and the roughness curve is expressed as y = Z(x), the following formula (4) can be used to determine the roughness.
[0151]
number
[0152] The ten-point average roughness (Rzjis) of the resin layer surface is preferably 70 nm or more, more preferably 90 nm or more, even more preferably 120 nm or more, and particularly preferably 140 nm or more. The upper limit is not particularly limited, but is preferably 800 nm, more preferably 600 nm, even more preferably 500 nm, and even more preferably 450 nm. If the ten-point average roughness (Rzjis) is equal to or greater than the lower limit, the resin layer can be said to have a sufficient uneven structure. If the ten-point average roughness (Rzjis) is equal to or less than the upper limit, the uneven structure of the resin layer can be said to have a sufficiently fine shape.
[0153] Ten-point average roughness (Rzjis) is one of the line roughness parameters (JIS B 0601:2013), and represents the sum of the average of the five greatest peak heights (Zp) and the average of the five greatest valley depths (Zv) on a profile curve over a reference length L, and is calculated using the following formula (5).
[0154]
number
[0155] The arithmetic mean roughness (Ra) and ten-point mean roughness (Rzjis) can be adjusted by the composition and contents in the present composition.
[0156] The load length ratio (Rmr(90)), arithmetic mean roughness (Ra) and ten-point mean roughness (Rzjis) of the resin layer surface are measured by the method described in the Examples using an atomic force microscope (scanning probe microscope). Measurement using an atomic force microscope (scanning probe microscope) makes it possible to capture a finer structure of the surface, and to obtain values that strongly reflect the effect of the resin layer.
[0157] The static friction coefficient between the resin layer surface and the opposite surface of the present laminated polyester film is preferably 1.0 or less, more preferably 0.8 or less, and further preferably 0.6 or less. When the present laminated polyester film is wound into a roll, the resin layer surface and the opposite surface come into contact with each other, and therefore the coefficient of friction between the resin layer surface and the opposite surface is important. Therefore, when the static friction coefficient is within this range, the uneven structure of the present resin layer provides good slipperiness, improving the handleability of the present laminated polyester film. The static friction coefficient can be measured by the method described in the Examples.
[0158] The air leakage index can be used as an index for evaluating the handling properties, such as the winding properties, of the present laminated polyester film. If the air leakage index is low, the air trapped when the present laminated polyester film is wound up can be easily released, and defects in the roll appearance, such as wrinkles and uneven edges, can be prevented. On the other hand, if the air leakage index is high, the trapped air can escape after a sufficient amount of time has passed, especially during transportation, causing problems such as the film shifting in the direction of the winding core or scratches due to the shifting.
[0159] The air leakage index is preferably, for example, 190,000 seconds or less. If it is 190,000 seconds or less, it tends to have good handling properties. The air leakage index is more preferably 130,000 seconds or less, even more preferably 100,000 seconds or less, even more preferably 60,000 seconds or less, even more preferably 50,000 seconds or less, and even more preferably 30,000 seconds or less. In addition, the air leakage index can be improved by the uneven structure of the resin layer, and can also be improved by the roughness of the smooth surface of the polyester film. As described above, it is preferable that the arithmetic mean height (Sa) of the surface opposite to the surface on which the resin layer is formed (i.e., the smooth surface) is 15 nm or less, and the maximum peak height (Sp) is 800 nm or less, or both of them are satisfied. In this case, the air leakage index is preferably 10,000 seconds or less, more preferably 8,000 seconds or less, and even more preferably 7,000 seconds or less. Here, the opposite surface is preferably the film surface used for processing when the laminated polyester film is used for various applications such as a release film for forming a green sheet for a laminated ceramic capacitor, a substrate for interlayer insulating resin release, and a substrate for dry film resist, and for example, various materials are preferably coated or laminated, as described later. On the other hand, when more precise processing is required, it is more preferable that the arithmetic mean height (Sa) of the opposite side (i.e., the smooth side of the film used for processing) is 9 nm or less, and the maximum peak height (Sp) is 500 nm or less, as described above. In this case, the air leakage index is preferably 130,000 seconds or less, more preferably 100,000 seconds or less, even more preferably 70,000 seconds or less, and particularly preferably 50,000 seconds or less. In this way, when the smooth side of the film is extremely smooth, more precise processing can be performed by utilizing the smoothness of the film, and the uneven structure of the resin layer improves the air leakage index to the above range, improving the winding property and improving the handling property of the laminated polyester film. In this way, since the air leakage index depends on the degree of smoothness of the side opposite to the side on which the resin layer is formed, it is preferable to set the numerical range according to each degree of smoothness. More specifically, by setting the air leakage index in each of the above numerical ranges, the effect of improving the handleability due to the uneven structure of the resin layer can be obtained, which is preferable. The air leakage index can be measured by the method described in the Examples.
[0160] <<Surface free energy>> Surface free energy is composed of the sum of components of intermolecular forces. The intermolecular forces are classified into dispersion force, orientation force, induction force, and hydrogen bond force, which respectively constitute surface free energy as a dispersion component (Dispersion), a polar component (Polar), an induction component (Induction), and a hydrogen bond component (Hydrogen). Of these components, the inductive components are very weak and can be ignored, and the hydrogen bonding components can be grouped together in the polar components.
[0161] In the present invention, the surface free energy γ SV Each component (variance component γ SV d and the polar component γ SV p ) is a value determined by the following measurement and calculation methods. First, the following γ LV1 , γ LV1 d and γ LV1 p The contact angle (θ1) between the first liquid and the surface of the resin layer to be measured, and γ LV2 , γ LV2 d and γ LV2 p The contact angle (θ2) between the second liquid, the contact angle of which is known, and the surface of the resin layer to be measured is measured. Next, these values are substituted into the following formulas (I-1) and (I-2), and the surface free energy γ of the resin layer surface to be measured is calculated from the simultaneous equations (I-1) and (I-2) below. SV The variance component of γ SV d and the polar component γ SV p In both cases, the units are mN / m.
[0162] (γ SV d ·γ LV1 d ) 1 / 2 +(γ SV p ·γ LV1 p ) 1 / 2 =γ LV1 (1+cosθ1) / 2 (I-1) (γ SV d ·γ LV2 d ) 1 / 2 +(γ SV p ·γ LV2 p ) 1 / 2 =γ LV2 (1+cosθ2) / 2 (I-2)
[0163] Gamma SV d : Surface free energy of the resin layer surface γ SV Variance components of Gamma SV p : Surface free energy of the resin layer surface γ SV Polar component of Gamma LV1 : surface tension of the first liquid Gamma LV2 : surface tension of the second liquid θ1: contact angle of the first liquid θ2: Contact angle of the second liquid Gamma LV1 d : Dispersive component of the surface tension of the first liquid Gamma LV1 p : Polar component of the surface tension of the first liquid Gamma LV2 d : Dispersive component of the surface tension of the second liquid Gamma LV2 p : the polar component of the surface tension of the second liquid
[0164] The above formulas (I-1) and (I-2) are derived from the following Owens-Wendt-Rable-Kaelble (OWRK) theoretical formula and the following Young's formula: Theoretical formula of OWRK: Gamma SL =γ SV +γ LV -2(γ SV d ·γ LV d ) 1 / 2 -2(γ SV p ·γ LV p ) 1 / 2 Young's formula: Gamma SV =γ SL +γ LV cosθ (wherein, γ SL is the interfacial tension between the resin layer surface and the liquid.)
[0165] In the present laminated polyester film, the polar component term in the surface free energy of the present resin layer is 5 mN / m or less. If the polar component term of the surface free energy is 5 mN / m or less, it is considered that a low polarity compound is unevenly distributed on the surface of the resin layer. This improves the slipperiness of the resin layer surface, thereby improving the coating film retention. The lower the polar component term of the surface free energy, the better, but it is preferably 4 mN / m or less, more preferably 3 mN / m or less, even more preferably 2.5 mN / m or less, even more preferably 2 mN / m or less, particularly preferably 1.5 mN / m or less, and most preferably 1 mN / m or less. The lower limit is usually greater than 0, and may be, for example, 0.05 mN / m or 0.08 mN / m. The coating retention of the resin layer is preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, still more preferably 85% or more, and still more preferably 90% or more. The upper limit of the coating retention is not particularly limited, and is 100% or less. If the coating retention is within this range, it is easy to prevent the inherent performance of the laminated polyester film from being impaired due to peeling or falling off of the coating, and to prevent process contamination due to the fallen coating.
[0166] The polar component term in the surface free energy of the resin layer can be adjusted by the composition and content in the composition, the thickness of the resin layer, and the like. In adjusting the composition, for example, when using a low polarity compound (A) and a binder resin (B) and / or a crosslinking agent (C), it is preferable to select a binder resin (B) and / or a crosslinking agent (C) that is poorly compatible with the low polarity compound (A). It is also effective to increase the content of the low polarity compound (A) in the composition and decrease the content of the binder resin (B) and / or the crosslinking agent (C). With regard to the thickness of the resin layer, it is also effective to increase the thickness in consideration of the composition of the composition. In addition, it is also effective to adopt wax as the low polarity compound (A) from the viewpoint that it is easy to repel other components in the molten state when forming the resin layer. By using these methods given as examples, the low polarity compound (A) is more likely to be unevenly distributed on the surface of the resin layer, and the polar component term in the surface free energy of the resin layer can be easily adjusted to a desired value. The surface free energy of the resin layer surface can be measured by the method described in the Examples.
[0167] <<<Applications of laminated polyester film>>> This resin layer is characterized in that it is made of a resin composition containing a specific compound and has a specific roughness structure, so that even a thin film can form a phase separation structure and express a fine uneven structure. Another characteristic is that it focuses on the load length ratio (Rmr(90)), which represents the unevenness distribution of the uneven structure, as an index of the roughness structure. This design concept has made it possible to precisely control the fine uneven structure, which was difficult to achieve with conventional particle-kneading film manufacturing methods. In addition, the specific roughness structure has made it possible to improve the ease of air escape even in a thin film, making it possible to provide a laminated polyester film with excellent handling properties.
[0168] The present laminated polyester film can be used for various applications for the purpose of improving the handleability, and the applications are not particularly limited. Among them, as described above, since it has a fine uneven structure, when used for sheet molding, it has the advantage that it exhibits good winding properties and is less likely to cause wrinkles even when a highly smooth film is wound into a roll, and it can be suitably used as a polyester film for sheet molding. Examples of polyester films for sheet molding include green sheet molding for multi-layer ceramic capacitors (MLCCs), interlayer insulating resins, dry film resists (DFRs), and multilayer circuit boards, and various other release and process applications. In release and process applications, the laminated polyester film is used, for example, as a support. The polyester film for sheet molding may be used, for example, in a process of forming various sheets such as green sheets by applying or laminating various materials on at least one side of the film. When the resin layer is provided only on one side, the various materials are preferably applied or laminated on the film side opposite to the side on which the resin layer is provided (opposite side), but may be applied or laminated on the film side on which the resin layer is provided. In addition, in the polyester film for sheet molding, a release layer or the like may be appropriately provided on the film side opposite to the side on which the resin layer is provided. In particular, the laminated polyester film is preferably used for manufacturing MLCCs.
[0169] Using this laminated polyester film, a multilayer ceramic capacitor (MLCC) is manufactured as follows. For example, a ceramic slurry containing a ceramic component and a binder resin is applied to the laminated film, preferably on the surface opposite to the resin layer of the laminated polyester film, and dried to produce a ceramic green sheet (dielectric sheet). Then, electrodes are printed on the laminated film by screen printing or the like to form internal electrodes, and after drying, the printed ceramic green sheet is peeled off from the release film (the laminated polyester film), and a large number of such green sheets are laminated. The laminated green sheets are pressed to be integrated, and then cut into individual chips. Then, the internal electrodes and dielectric layers are sintered in a firing furnace to obtain a multilayer ceramic capacitor. Thus, the laminated polyester film of the present invention is preferably used as a support for ceramic green sheets in the production process of a laminated ceramic capacitor.
[0170] <<<Terminology>>> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES
[0171] The present invention will now be described in further detail with reference to examples. However, the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention.
[0172] <Evaluation method> (1) Intrinsic viscosity (IV) of polyester 1 g of polyester from which components incompatible with the polyester had been removed was precisely weighed out, dissolved in 100 mL of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and the viscosity was measured at 30 °C using a viscosity measuring device "VMS-022UPC·F10" (manufactured by Rigo Co., Ltd.).
[0173] (2) Average particle size The average particle size of particles was determined by observing 10 or more particles with a scanning electron microscope (SEM), measuring the diameters of the particles, and averaging the diameters (average primary particle size). In the case of non-spherical particles, the average of the longest and shortest diameters was measured as the diameter of each particle.
[0174] (3) Rough structure of the resin layer Measurements were carried out under the following conditions using a scanning probe microscope (Shimadzu Corporation, SPM-9700). Tip: Silicon cantilever Scanning mode: Dynamic mode Scanning range: 25μm×25μm Scan speed: 0.8Hz Pixel count: 512 x 512 data points From the obtained data, a 25 μm-wide cross-sectional shape was observed, and if there were multiple convex or concave portions with a step height of more than 10 nm at 80% or more of the positions, it was judged as "present" as an uneven structure, and if multiple convex or concave portions could not be confirmed, it was judged as "absent" as an uneven structure.
[0175] (4) Hansen solubility parameters (HSP) of each resin [δd, δp, δh] Approximately 0.05 g of solids of each resin was placed in a 20 mL glass bottle, and a solvent was added so that the solid ratio was 1 mass %. After stirring for 20 seconds, the bottle was left to stand in a 23 ° C environment. After 24 hours, the glass bottle was checked, and if the solids dissolved, the solvent used was judged to be a good solvent, and if the solids were insoluble or swollen, the solvent used was judged to be a poor solvent, and each parameter of the Hansen solubility parameter (HSP) [δd, δp, δh] was calculated. The commercially available Hansen solubility parameter calculation software HSPiP was used to calculate the values. The solvent types used were selected according to Table 1 above, and a total of 21 types of solvents were used for the evaluation.
[0176] (5) Hansen Solubility Parameter (HSP) Distance Using the HSP values measured by the method (4) above, the HSP distance between each of the components (A) and (B) used was calculated from the following formula. HSP distance={4×(δd1-δd2) 2 +(δp1-δp2) 2 +(δh1-δh2) 2} 0.5 Here, δd1, δp1, and δh1 represent δd, δp, and δh of component (A), respectively, in the Hansen solubility parameters [δd, δp, δh], and δd2, δp2, and δh2 represent δd, δp, and δh of component (B), respectively. Note that δp1≦δp2.
[0177] (6) Arithmetic mean roughness (Ra) and ten-point mean roughness (Rzjis) of the resin layer surface From the data of the scanning probe microscope measured by the method (3) above, a cross-sectional analysis of 25 μm width was performed parallel to the tenter stretching direction (i.e., the transverse direction) to obtain the arithmetic mean roughness (Ra) and ten-point mean roughness (Rzjis). Cross-sectional analysis data was obtained at 10 points at equal intervals in the film formation direction (i.e., the longitudinal direction), and these were averaged to obtain the arithmetic mean roughness (Ra) and ten-point mean roughness (Rzjis).
[0178] (7) Load length ratio of resin layer surface (Rmr(90)) Cross-sectional analysis was performed using a scanning probe microscope in the same manner as in (6) above, and the load length ratio at 90% of the cutting level (Rmr(90)) was calculated. Cross-sectional analysis data was obtained at 10 points at equal intervals in the film formation direction (i.e., the machine direction), and the average was calculated.
[0179] (8) Coefficient of static friction The static friction coefficient between the resin layer surface and the opposite surface of the laminated polyester film was determined by the following method. A film was attached to a smooth glass plate having a width of 10 mm and a length of 100 mm so that the surface opposite to the surface on which the resin layer was provided was the upper surface. A film cut to a width of 18 mm and a length of 120 mm was placed on top of the film so that the surface on which the resin layer was provided was the lower surface, and a metal pin having a diameter of 8 mm was pressed onto the film, and the metal pin was slid in the longitudinal direction of the glass plate with a load of 30 g at 40 mm / min to measure the friction force, and the maximum value immediately after the sliding was evaluated as the static friction coefficient. The measurement was performed in an atmosphere of room temperature 23±1°C and humidity 50±0.5%RH. The number of measurements (N) was 10, and the average value was used. Static friction coefficient (μs) = Fs / weight (In the above formula, the units of Fs and Fd are g-force, and the unit of weight load is g-force.)
[0180] (9) Air leakage index A DigiBec smoothness tester (manufactured by Toyo Seiki Co., Ltd., "DB-2") was used to measure in accordance with JIS P8119:1998 under an atmosphere of 23°C temperature and 50% RH. The pressure of the pressurizing device was 100 kPa, and the vacuum container had a volume of 38 ml. The time it took for 1 mL of air to flow, i.e., the time (seconds) for the pressure inside the container to change from 50.7 kPa to 48.0 kPa, was measured, and the air leakage index was calculated by multiplying the number of seconds obtained by the measurement. The sample size of the test film was 70 mm square, and 20 sheets of the test film were laminated so that the front and back of the test film overlapped to form a test laminate film. A 5mm hole was made in the center of the test laminate film, and the air leakage index was measured as described above. The higher the air leakage index value, the longer it takes for air to leak through the gaps between the films, indicating that the films are more closely attached to each other, and therefore the greater the risk of wrinkles occurring when the film is rolled up.
[0181] (10) Polar component term in surface free energy The contact angle was measured using a contact angle meter DMo-501 manufactured by Kyowa Interface Science Co., Ltd., and 2 μL of pure water, methylene iodide, and ethylene glycol were dropped onto a film that had been conditioned for 24 hours or more in an environment of 23°C and 50% RH. Using the contact angle obtained and the surface tension component values of each liquid (Table 2), the polar component of the surface free energy of the resin layer surface was calculated according to the Owens-Wendt-Rable-Kaelble (OWRK) theoretical formula.
[0182] [Table 2]
[0183] (11) Coating retention rate A BEMCOT ("M-3II" manufactured by Asahi Kasei Fibers Corporation) impregnated with 4 mL of methyl ethyl ketone was attached to a rubbing tester (manufactured by Ohira Rika Kogyo Co., Ltd.) and rubbed five times on the resin layer surface of the sample film with an arm load of 680 g. The resin layer surface before and after treatment was measured by X-ray fluorescence analysis (XRF) to measure the amount of components derived from the resin layer. The retention rate of the coating was calculated by the following formula. Coating retention rate (%) = (amount of resin layer component after treatment / amount of resin layer component before treatment) x 100
[0184] <Materials used> In the examples and comparative examples, pellets of polyethylene terephthalate homopolymer (intrinsic viscosity: 0.64 dL / g) were used.
[0185] Coating solutions 1 to 13 were prepared by diluting the resin compositions obtained by stirring and mixing the compositions shown in Table 4 below with water. The components used are as follows. The Hansen parameters of each component are shown in Table 3.
[0186] (B) Binder resin; components (IA) to (IH) [Component (IA)] A water dispersion of a polyester resin copolymerized in the following composition. Monomer composition: (acid component) 2,6-naphthalenedicarboxylic acid / 5-sodium sulfoisophthalic acid / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%)
[0187] [Ingredients (IB)] A water dispersion of a polyester resin copolymerized in the following composition. Monomer composition: (acid component) 2,6-naphthalenedicarboxylic acid / 5-sodium sulfoisophthalic acid / (diol component) ethylene glycol / diethylene glycol = 94 / 6 / / 90 / 10 (mol%)
[0188] [Ingredients (IC)] A water dispersion of a polyester resin copolymerized in the following composition. Monomer composition: (acid component) terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / / (diol component) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (mol%)
[0189] Component (ID) A water dispersion of a polyester resin copolymerized in the following composition. Monomer composition: (acid component) terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / / (diol component) ethylene glycol / neopentyl glycol = 49 / 48 / 3 / / 50 / 50 (mol%)
[0190] [Component (IE)] A water dispersion of a polyester-based urethane resin polymerized according to the following composition. Isophorone diisocyanate unit / terephthalic acid unit / isophthalic acid unit / ethylene glycol unit / diethylene glycol unit / dimethylolpropionic acid unit=12 / 19 / 18 / 21 / 25 / 5 (mol%)
[0191] [Component (IF)] When a polyester polyol containing 282 parts by mass of terephthalic acid, 282 parts by mass of isophthalic acid, 62 parts by mass of ethylene glycol, and 250 parts by mass of neopentyl glycol is designated as (C1a), a polyester polyurethane containing 876 parts by mass of (C1a), 244 parts by mass of tolylene diisocyanate, 81 parts by mass of ethylene glycol, and 67 parts by mass of dimethylolpropionic acid is neutralized with ammonia and dispersed in water (non-volatile content concentration 20%, viscosity at 25°C 50 mPa s).
[0192] [Ingredients (IG)] A water dispersion of a mixture of a polycarbonate-based urethane resin and a (meth)acrylate compound having the following composition. An aqueous dispersion of a mixture of (meth)acrylate compounds excluding urethane (meth)acrylate and urethane (meth)acrylate, which is a mixture of 50 parts by mass of a polyurethane (meth)acrylate resin formed from polyhexamethylene carbonate diol units having a molecular weight of 1,100, dimethylolpropionic acid units, hydrogenated xylylene diisocyanate units, and dipentaerythritol pentaacrylate units in a ratio of 11 / 7 / 40 / 42 (mol %), 27 parts by mass of dipentaerythritol hexaacrylate, and 23 parts by mass of trimethylolpropane triacrylate.
[0193] [Ingredients (IH)] An aqueous dispersion of a mixture of an acrylic resin and an oxazoline compound polymerized in the following composition. An aqueous dispersion of a mixture of 90 parts by mass of an acrylic resin formed from methyl methacrylate / ethyl acrylate=64 / 36 (mass%) and 10 parts by mass of an oxazoline compound.
[0194] [Component (II)] ((A) low polar compound) 300g of oxidized polyethylene wax with a melting point of 105°C, acid value of 16mgKOH / g, density of 0.93g / mL and number average molecular weight of 5000, 650g of ion-exchanged water, 50g of decaglycerin monooleate surfactant and 10g of 48% potassium hydroxide aqueous solution were added to a 1.5L emulsification equipment equipped with a stirrer, thermometer and temperature controller, and the contents were replaced with nitrogen, sealed and stirred at high speed at 150°C for 1 hour, then cooled to 130°C and passed through a high-pressure homogenizer at 400 atmospheres to produce a wax emulsion cooled to 40°C.
[0195] [Component (III)] ((C) Crosslinking agent) Melamine compound: Hexamethoxymethylolmelamine
[0196] [Component (IVA)] ((E) particles) Silica particles with an average particle size of 5 nm
[0197] [Component (IVB)] ((E) particles) Silica particles with an average particle size of 200 nm
[0198] [Component (V)] ((D) Crosslinking catalyst) 2-Amino-2-methylpropanol hydrochloride
[0199] [Table 3]
[0200] Example 1 The polyester pellets were melted at 285° C., extruded onto a cooling roll set at 40° C., and cooled and solidified to obtain an unstretched sheet. Next, this film was stretched 3.5 times in the longitudinal direction while passing through a group of heated rolls at 85°C to obtain a uniaxially stretched film. Coating solution 1 having the composition shown in Table 2 below was applied to one side of this uniaxially stretched film in an amount (after drying and stretching) of 0.07 g / m 2 The film was then introduced into a tenter stretching machine, stretched 4.5 times in the width direction at 100°C, and further heat-treated at 235°C, followed by 2% relaxation in the width direction to obtain a laminated polyester film with a thickness of 31 µm. The evaluation results are shown in Table 5.
[0201] [Table 4]
[0202] (Examples 2 to 5, 7 to 8, and 10) A laminated polyester film was obtained in the same manner as in Example 1, except that the coating solution shown in Table 2 was used. The evaluation results are shown in Table 5.
[0203] Example 6 Coating solution 6 shown in Table 2 was applied in an amount of 0.09 g / m after drying and stretching. 2 Except for coating, a laminated polyester film was obtained in the same manner as in Example 1. The evaluation results are shown in Table 5.
[0204] (Examples 9, 11 to 12) The coating amount of the coating solution shown in Table 2 (after drying and stretching) was 0.05 g / m2 Except for coating, a laminated polyester film was obtained in the same manner as in Example 1. The evaluation results are shown in Table 5.
[0205] Comparative Example 1 Except for not providing a resin layer, a polyester film was obtained in the same manner as in Example 1. The evaluation results are shown in Table 5.
[0206] Comparative Example 2 A laminated polyester film was obtained in the same manner as in Example 1, except for using Coating Liquid 12 shown in Table 2. The evaluation results are shown in Table 5.
[0207] (Comparison 3) The coating solution 13 shown in Table 2 was applied in an amount of 0.10 g / m after drying and stretching. 2 Except for coating, a laminated polyester film was obtained in the same manner as in Example 1. The evaluation results are shown in Table 5.
[0208] [Table 5]
[0209] As the results in Table 5 show, by setting the polar component of the surface free energy to 5 mN / m or less, the retention rate of the coating film can be improved, resulting in a film with excellent durability. In addition, the laminated polyester film of the present invention has a load length ratio (Rmr(90)) at a break level of 90% of 95% or less, thereby forming an appropriate uneven shape, a low static friction coefficient of 1 or less, thereby providing good slipperiness, and an air leakage index of 50,000 seconds or less, thereby providing excellent air escape properties. This shows that the film has excellent productivity, such as excellent winding properties. On the other hand, Comparative Example 1 does not have a resin layer and therefore does not have a concave-convex structure. Therefore, it can be said that the film has a high air leakage index and poor handling properties. In addition, Comparative Examples 2 and 3 have a polar component of the surface free energy greater than 5 mN / m, so the coating retention rate after rubbing treatment is poor and the film has poor durability. [Industrial Applicability]
[0210] It is found that the laminated polyester film of the present invention maintains its coating even after rubbing treatment and has high durability. In addition, since the surface of the resin layer has a fine uneven structure with high coating strength, when the film is used for sheet molding, for example, the film has an advantage that it exhibits good winding properties and is less likely to wrinkle even when wound into a roll. Furthermore, since the resin layer of the laminated polyester film of the present invention can be made thin, it is possible to accommodate a thin and long polyester film, which can contribute to improving productivity by reducing the frequency of changing product rolls during processing. Therefore, the laminated polyester film of the present invention has high durability and excellent surface smoothness and can be suitably used as a polyester film for sheet molding, etc., and is of great industrial utility.
Claims
1. A laminated polyester film having a resin layer formed from a resin composition on at least one side of a polyester film, the resin layer having a polar component term in the surface free energy of 5 mN / m or less.
2. The laminated polyester film according to claim 1 , wherein the resin composition further comprises (A) a low-polarity compound.
3. The laminated polyester film according to claim 1 , wherein the resin composition further comprises a binder resin (B).
4. The laminated polyester film according to claim 1 , wherein the resin composition further comprises (C) a crosslinking agent.
5. The laminated polyester film according to any one of claims 1 to 4, wherein the load length ratio (Rmr(90)) of a roughness curve at a cutting level of 90% of the surface of the resin layer is 95% or less when measured with a scanning probe microscope.
6. 5. The laminated polyester film according to claim 1, wherein the resin layer has a surface having an arithmetic average roughness (Ra) of 15 nm or more as measured by a scanning probe microscope.
7. 5. The laminated polyester film according to claim 1, wherein the ten-point average roughness (Rzjis) of the surface of the resin layer measured by a scanning probe microscope is 70 nm or more.
8. The laminated polyester film according to any one of claims 1 to 4, wherein the resin layer has an uneven structure.
9. The laminated polyester film according to any one of claims 1 to 4, which has an air leakage index of 190,000 seconds or less.
10. 3. The laminated polyester film according to claim 2, wherein the low-polarity compound (A) comprises at least one selected from the group consisting of waxes and compounds containing a long-chain alkyl group.
11. The laminated polyester film according to claim 3 , wherein the binder resin (B) comprises at least one resin selected from the group consisting of a polyester resin, a (meth)acrylic resin, and a polyurethane resin.
12. The laminated polyester film according to claim 4 , wherein the crosslinking agent (C) is a melamine compound.
13. The laminated polyester film according to any one of claims 1 to 4, wherein the resin composition contains a crosslinking catalyst (D).
14. The laminated polyester film according to any one of claims 1 to 4, wherein the resin composition comprises (E) particles.
15. The laminated polyester film according to any one of claims 1 to 4, which is used as a support for a ceramic green sheet in a process for producing a laminated ceramic capacitor.
16. 5. Use of the laminated polyester film according to claim 1 as a support for a ceramic green sheet in a process for producing a laminated ceramic capacitor.
17. A method for producing a ceramic green sheet, comprising coating a slurry containing a ceramic component on a surface of the laminated polyester film according to any one of claims 1 to 4 opposite to the resin layer.
Citation Information
Patent Citations
Hard coat film
JP2013010323A
Mold release film and method for producing the same
JP2013060555A
Release film for molding ceramic sheet
JP2015033811A
Laminate
JP2021024177A
Cited By
Recycled film
WO2026058619A1